Compositions and methods for tunable magnetic nanoparticles

By developing nanoparticle compositions containing magnetic nanoparticles and amine-functionalized dextran coatings, the chemical linker stability problems and the lack of tunable magnetic and surface functionalization in existing contrast agents are solved, and high-quality multimodal contrast agents are achieved, suitable for medical imaging and treatment.

CN115066265BActive Publication Date: 2025-04-11THE GENERAL HOSPITAL CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202080095773.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-05
Filing Date
2020-12-07
Publication Date
2025-04-11
Estimated Expiration
2040-12-07

AI Technical Summary

Technical Problem

The stability of existing multimodal contrast agents in chemical linking groups in cells and tissues leads to solid separation, reduces the quality and usefulness of the contrast agent, and lacks tunable surface functionalization and magnetic properties.

Method used

A nanoparticle composition is developed, including magnetic nanoparticles (prepared from ferric chloride, ferrous chloride or a combination thereof) and a dextran coating that is finely tuned by amine functionalization to achieve tunable surface modification and magnetic properties.

Benefits of technology

A multimodal contrast agent that is suitable in clinical practice is realized, with stable magnetic properties and tunable surface functionalization, improving the quality and usefulness of the contrast agent, and can be effectively used in medical imaging and disease treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115066265B_ABST
    Figure CN115066265B_ABST
Patent Text Reader

Abstract

The present disclosure provides nanoparticle compositions for the treatment, prevention, or imaging of diseases (e.g., cancer), methods of treating diseases, preventing diseases, or imaging diseases with the nanoparticle compositions in subjects in need thereof, and methods of preparing the nanoparticle compositions of the present disclosure. The nanoparticle compositions may include magnetic nanoparticles of ferric chloride, ferrous chloride, or a combination thereof, and a dextran coating functionalized with one or more amine groups.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of U.S. Provisional Application No. 62 / 943,927, filed on December 5, 2019. The entire contents of the foregoing application are incorporated herein by reference in their entirety. Technical Field

[0003] The present disclosure provides nanoparticle compositions with tunable magnetic properties and tunable surface modifications (e.g., amine modifications), methods for preparing these nanoparticle compositions, and methods for using these nanoparticle compositions. The nanoparticle compositions may include ferrous chloride, ferric chloride, dextran, or any combination thereof. Background Art

[0004] Medical imaging is used to collect information about a subject. In some types of imaging, a contrast agent is administered to the subject. The contrast agent selectively binds to biological particles or other structures of interest in the subject. The contrast agent is then detected using a medical imaging device, and the collected information is used to develop an image, etc.

[0005] Although a lot of information can be obtained even from a single medical image, multiple imaging techniques are needed to provide comprehensive quantitative diagnostic information with high spatiotemporal resolution, high detection sensitivity, and tomographic capabilities. In the past, this often meant administering multiple contrast agents to a single subject for each modality performed.

[0006] Multimodal contrast agents have been developed that are suitable for detection by various types of modalities. These multimodal contrast agents typically include multiple entities, each of which can be detected by a separate modality. The multiple entities are typically linked together using chemical linkers to prepare particles that each contain all of the corresponding multiple entities. However, chemical linkers often have variable stability in cells and tissues or over time, meaning that some entities may dissociate, thereby reducing the quality and usefulness of these contrast agents.

[0007] In order to avoid the problem of chemically linking multiple entities together, some people have attempted to form contrast agents with core-shell structures. However, to date, there are significant problems in developing clinically applicable core-shell structures. In addition, currently available particles lack tunable surface functionalization and tunable magnetism using targeting moieties.

[0008] Therefore, there is a need for a multimodal contrast agent that is clinically applicable and provides design flexibility in terms of surface functionalization and physical properties (eg, magnetic properties). Summary of the invention

[0009] Certain aspects of the present disclosure relate to a nanoparticle composition comprising: a magnetic nanoparticle comprising: ferric chloride, ferrous chloride, or a combination thereof; and a dextran coating functionalized with one or more amine groups, wherein the one or more amine groups range in number from about 5 to about 1000.

[0010] In some embodiments, the nanoparticle composition comprises about 50 weight (wt) % to about 100 weight % of ferric chloride and about 0 weight % to about 50 weight % of ferrous chloride. In some embodiments, the nanoparticle composition comprises about 0.65 g of ferric chloride and about 0.4 g of ferrous chloride. In some embodiments, the number of one or more amine groups ranges from about 5 to about 150. In some embodiments, the nanoparticle composition comprises about 50 weight % to about 100 weight % of ferric chloride. In some embodiments, the nanoparticle composition comprises about 1.2 g of ferric chloride. In some embodiments, the nanoparticle composition does not comprise ferrous chloride. In some embodiments, the number of one or more amine groups ranges from about 246 to about 500.

[0011] In another aspect, the present disclosure relates to a nanoparticle composition comprising: magnetic nanoparticles comprising: ferric chloride, ferrous chloride, or a combination thereof; and a dextran coating, wherein the nonlinear index of the magnetic nanoparticles ranges from about 6 to about 40.

[0012] In some embodiments, the nanoparticle composition comprises about 50 weight (wt) % to about 80 weight % of ferric chloride and about 50 weight % to about 20 weight % of ferrous chloride. In some embodiments, the nanoparticle composition comprises about 0.54 g of ferric chloride and about 0.2 g of ferrous chloride. In some embodiments, the nonlinear index of the magnetic nanoparticles ranges from 8 to 14. In some embodiments, the nanoparticle composition comprises about 0 weight (wt) % to about 50 weight % of ferric chloride and about 100 weight % to about 50 weight % of ferrous chloride, or about 80 weight % to about [100 weight %] of ferric chloride and about 0 weight % to about 20 weight % of ferrous chloride. In some embodiments, the nanoparticle composition comprises about 0.54 g of ferric chloride and about 0.4 g of ferrous chloride. In some embodiments, the nonlinear index of the magnetic nanoparticles ranges from about 8 to about 67. In some embodiments, the nonlinear index of the magnetic nanoparticles is about 67. In some embodiments, the magnetic nanoparticles have an iron oxide core having a diameter of about 3 nm to about 50 nm, and the hydrodynamic diameter of the magnetic nanoparticles is about 7 nm to about 200 nm.

[0013] In some embodiments, the polydispersity of magnetic nanoparticles is about 0.1 to about 0.25. In some embodiments, the dextran coating comprises a dextran with a molecular weight range of about 1kDa to about 15kDa. In some embodiments, the dextran coating comprises a dextran with a molecular weight of about 10kDa. In some embodiments, the nanoparticle composition further comprises a drug payload (payload) attached to the surface of the dextran coating. In some embodiments, the drug payload is an oligonucleotide conjugated to one or more amine groups. In some embodiments, the drug payload is a drug, an antibody, a growth factor, a nucleic acid, a nucleic acid derivative, a nucleic acid fragment, a protein, a protein derivative, a protein fragment, a sugar, a polysaccharide fragment, a sugar derivative, a glycoside, a glycoside fragment, a glycoside derivative, an imaging contrast agent or any combination thereof.

[0014] In another aspect, the present disclosure relates to a pharmaceutical composition comprising any of the nanoparticle compositions of the present disclosure and at least one pharmaceutically acceptable carrier or diluent.

[0015] In another aspect, the present disclosure relates to a method for imaging a tissue target site in a subject in need thereof, the method comprising: administering a therapeutically effective amount of any nanoparticle composition of the present disclosure to at least the tissue target site at a portion of the subject's body, body part, tissue, cell, or body fluid; applying energy to the magnetic nanoparticle composition and the tissue target site; detecting signals from the nanoparticle composition and the tissue target site; and obtaining an image of the tissue target site based on the detected signals.

[0016] In some embodiments, the imaging is magnetic resonance imaging, magnetic particle imaging, or a combination thereof, and the energy is a magnetic field. In some embodiments, the disease is cancer, and the tissue target site is a tumor. In some embodiments, the nanoparticle composition accumulates at the target site of the subject.

[0017] In another aspect, the present disclosure relates to any composition of the present disclosure for use in a method of imaging a disease in a subject in need thereof.

[0018] In another aspect, the present disclosure relates to a method of preparing any of the nanoparticle compositions of the present disclosure, the method comprising: dissolving dextran in water; cross-linking the dextran with epichlorohydrin; preparing a ferrous chloride solution, a ferric chloride solution, or a combination thereof; preparing a mixture by adding the ferrous chloride solution, the ferric chloride solution, or a combination thereof to the dextran; adding a base to the mixture while stirring and subjecting the mixture to an ice bath; and subjecting the mixture to a temperature of about 75° C. to about 90° C., wherein the step of adding the base prevents the formation of iron oxide crystals, iron oxide hydrates, or a combination thereof, and wherein the mixture comprises about 50 weight (wt) % to 100 wt % ferric chloride and about 0 wt % to 50 wt % ferrous chloride.

[0019] In another aspect, the present disclosure relates to a method of preparing any of the nanoparticle compositions of the present disclosure, the method comprising: dissolving dextran in water; cross-linking the dextran with epichlorohydrin; preparing a ferrous chloride solution, a ferric chloride solution, or a combination thereof; preparing a mixture by adding the ferrous chloride solution, the ferric chloride solution, or a combination thereof to the dextran; adding a base to the mixture while stirring and subjecting the mixture to an ice bath; and subjecting the mixture to a temperature of about 75° C. to about 90° C., wherein the step of adding the base prevents the formation of iron oxide crystals, iron oxide hydrates, or a combination thereof, and wherein the mixture comprises 50 wt % to about 80 wt % ferric chloride and about 50 wt % to about 20 wt % ferrous chloride.

[0020] The term "magnetic" is used to describe compositions that respond to a magnetic field. Non-limiting examples of magnetic compositions (e.g., any of the nanoparticle compositions described herein) can include paramagnetic, superparamagnetic, ferromagnetic, or diamagnetic materials. Non-limiting examples of magnetic compositions include metal oxides selected from the group consisting of magnetite; ferrites (e.g., ferrites of manganese, cobalt, and nickel); Fe(II) oxides; and hematite, and metal alloys thereof. Additional magnetic materials are described herein and are known in the art.

[0021] The term "diamagnetic" is used to describe a composition that has a relative magnetic permeability less than or equal to 1 and that is repelled by a magnetic field.

[0022] The term "paramagnetic" is used to describe a composition that develops a magnetic moment only in the presence of an applied magnetic field.

[0023] The term "ferromagnetic" or "ferromagnetic" is used to describe a composition that is highly sensitive to magnetic fields and that retains its magnetic properties (magnetic moment) after the applied magnetic field is removed.

[0024] The term "nanoparticle" means an object having a diameter between about 2 nm and about 200 nm (e.g., between 10 nm and 200 nm, between 2 nm and 100 nm, between 2 nm and 40 nm, between 2 nm and 30 nm, between 2 nm and 20 nm, between 2 nm and 15 nm, between 100 nm and 200 nm, and between 150 nm and 200 nm). Non-limiting examples of nanoparticles include the nanoparticles described herein.

[0025] The term "magnetic nanoparticle" means a magnetic (as defined herein) nanoparticle (eg, any of the nanoparticles described herein). Non-limiting examples of magnetic nanoparticles are described herein. Additional magnetic nanoparticles are known in the art.

[0026] The term "nucleic acid" means any single-stranded or double-stranded polynucleotide (e.g., DNA or RNA, cDNA, semisynthetic or synthetic origin). The term nucleic acid includes oligonucleotides containing at least one modified nucleotide (e.g., containing a modification in the base and / or a modification in the sugar) and / or a modification in the phosphodiester bond connecting two nucleotides. In some embodiments, the nucleic acid may include at least one locked nucleic acid (LNA). Non-limiting examples of nucleic acids are described herein. Additional examples of nucleic acids are known in the art.

[0027] The term "imaging" means visualizing at least one tissue of a subject using biophysical techniques (e.g., electromagnetic energy absorption and / or emission). Non-limiting embodiments of imaging include magnetic resonance imaging (MRI), X-ray computed tomography, and optical imaging.

[0028] As used herein, the term "subject" or "patient" refers to any mammal (e.g., a human or veterinary subject, e.g., a dog, cat, horse, cow, goat, sheep, mouse, rat, or rabbit) to which the compositions or methods of the present disclosure may be administered, e.g., for experimental, diagnostic, preventive, and / or therapeutic purposes. A subject may be seeking or in need of treatment, requiring treatment, currently receiving treatment, about to receive treatment, or under the care of a trained professional for a particular disease or condition.

[0029] As used in the specification and the appended claims, the singular forms "a", "an", and "the" include plural referents unless the context clearly dictates otherwise. Thus, for example, reference to "a nanoparticle" includes mixtures of nanoparticles, reference to "a nanoparticle" includes mixtures of two or more such nanoparticles, etc.

[0030] Ranges may be expressed herein as from "about" one particular value and / or to "about" another particular value. When such a range is expressed, another embodiment includes from one particular value and / or to another particular value. Similarly, when a numerical value is expressed as an approximation, by using the aforementioned "about", it will be understood that the particular value forms another embodiment. It will be further understood that the endpoints of each range are important both relative to the other endpoint and independently of the other endpoint.

[0031] Certain embodiments of the present disclosure include methods for using any nanoparticle composition for treating diseases, preventing diseases, diagnosing diseases, and / or imaging diseases in subjects in need. There is currently a need for tunable and improved nanoparticle compositions that can meet the necessary requirements for successfully reaching target sites in the human body for treatment and / or imaging purposes. The nanoparticle compositions of the present disclosure and the methods using the nanoparticle compositions solve the above-mentioned necessary requirements. In some embodiments, the key physical properties of the nanoparticle composition (e.g., amination and magnetic intensity) can be fine-tuned by adjusting the concentration of certain components (e.g., the concentration of ferrous chloride or ferric chloride). In some embodiments, the nanoparticle composition can be amplified (scale-up) when the physical properties (e.g., amination, magnetic intensity, size, and polydispersity) remain unchanged. In some embodiments, the nanoparticle composition can have long-term stability (e.g., at least up to 6 months). In some embodiments, magnetic nanoparticles can be prepared by precipitation in an aqueous medium, which is environmentally friendly and cheaper than other synthetic methods.

[0032] In some embodiments, the methods of using the nanoparticle compositions described herein can prevent, treat, reduce and / or eliminate symptoms associated with a disease (e.g., cancer). In some embodiments, the methods of using the nanoparticle compositions described herein can contribute to the imaging of a target site (e.g., a tumor). In some embodiments, the nanoparticle compositions can be used to simultaneously image and treat a target site (e.g., a tumor) in a subject in need thereof.

[0033] In some embodiments, nanoparticle compositions enable sustained delivery of a payload (e.g., an oligonucleotide) to a target site (e.g., a tumor). In some embodiments, nanoparticle compositions are suitable for delivering a payload (e.g., an oligonucleotide) to a target site (e.g., a tumor or tumor core) that is usually difficult for a drug delivery vehicle to reach. In some embodiments, nanoparticle compositions are biocompatible and can be retained in the blood circulation with a half-life of about 0.25 hours to about 24 hours.

[0034] When numerical values ​​are described in ranges in the present disclosure, the endpoints are included. In addition, it should be understood that whether or not a specific numerical value or a specific sub-range is explicitly stated, the description includes disclosure of all possible sub-ranges within such ranges, as well as specific numerical values ​​falling within such ranges.

[0035] Other features and advantages of the disclosure will be apparent from the following detailed description and drawings, and from the claims.

[0036] Various embodiments of the features of the present disclosure are described herein. However, it should be understood that such embodiments are provided by way of example only, and that many changes, modifications, and substitutions may be made by those skilled in the art without departing from the scope of the present disclosure. It should also be understood that various alternatives to the specific embodiments described herein are also within the scope of the present disclosure.

[0037] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs. Methods and materials for use in the present invention are described herein; other suitable methods and materials known in the art may also be used. The materials, methods, and examples are illustrative only and are not intended to be limiting. All publications, patent applications, patents, sequences, database entries, and other references mentioned herein are incorporated herein by reference in their entirety. In the event of a conflict, the present specification, including definitions, will control.

[0038] The details of one or more embodiments of the invention are set forth in the accompanying drawings and the description below. Other features and advantages of the invention will become apparent from the following detailed description and drawings, and from the claims. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 An example of an apparatus for dextran dissolution during the method of preparing nanoparticles of the present disclosure is shown.

[0040] Figure 2 An example of an apparatus for dextran dissolution during the method of preparing nanoparticles of the present disclosure is shown.

[0041] Figure 3 The absorbance spectra of aminated dextran coated nanoparticles exposed to 6N-hydrochloric acid as determined by ultraviolet / visible (UV / Vis) spectroscopy are shown and the solution is monitored.

[0042] Figure 4 The size characteristics of the "Condition 1" nanoparticles were shown to have approximately 60-90 amine groups per magnetic nanoparticle (MNP); the size was approximately 11.48 nanometers (nm) as determined by dynamic light scattering.

[0043] Figure 5 The size characteristics of the "Condition 2" nanoparticles were shown to have approximately 250 amine groups per MNP; the size was approximately 15.6 nm as determined by dynamic light scattering.

[0044] Figure 6 Shown is the absorbance spectrum of "Condition 2" nanoparticles having approximately 250 amine groups per magnetic nanoparticle (MNP) as determined by UV / Vis spectroscopy.

[0045] Figure 7 Shown are the absorbance spectra of "Condition 1" nanoparticles having approximately 60-90 amine groups per magnetic nanoparticle (MNP) and "Condition 2" nanoparticles having approximately 246-500 amine groups per MNP as determined by UV / Vis spectroscopy.

[0046] Figure 8 Show the example of gel electrophoresis for analyzing oligonucleotide load in condition 1MNP.By changing the ratio of oligonucleotide (oligo) to amine group of each nanoparticle, the numerical value of oligonucleotide / magnetic nanoparticle (Oligo / MN) can be gradually increased.The Oligo / MN numerical value represents the molar ratio of oligonucleotide of each nanoparticle.The quantity of oligonucleotide is tested with 64 amine / MNP, and the reaction ratio is changed so that the load of oligonucleotide is maximized.These MNPs are passed through the conditions in table 3 (i.e., Fe 3 + / Fe 2+ The MNPs were synthesized in the presence of excess ammonium hydroxide addition.

[0047] Fig. 9 Magnetic particle spectrometry is shown for quantifying the magnetic properties of the nanoparticles. As the primary criterion for magnetic properties, the nonlinear index is compared between samples with the indicated formulations.

[0048] Fig.10 As determined by dynamic light scattering, Fe 3+ :Fe 2+ The example nanoparticles having a ratio of 1:1 and a nonlinear index of 12.1 had an average nanoparticle size of about 149.3 nm and a standard deviation of 0.9 nm.

[0049] Fig.11 Magnetic particle spectroscopy for quantifying the magnetic properties of nanoparticles is shown. The nonlinear index of the nanoparticles synthesized according to "Condition B" shown in Table 4 was calculated to be 9.7111.

[0050] Fig.12 As determined by dynamic light scattering, Fig.11 The average nanoparticle size of the nanoparticles was about 127.1 nm and the standard deviation was 0.21 nm.

[0051] Fig.13 and Fig.14 The magnetic particle spectroscopy method used to quantify the magnetic properties of the nanoparticles is shown. The nonlinear index of the nanoparticles synthesized according to "Condition C" shown in Table 4 was calculated as Fig.13 8.84556 as shown in Fig.14 This assay was performed 1 month after synthesis to check the stability of the nanoparticles.

[0052] Fig.15 As determined by dynamic light scattering, Fig.14 The average nanoparticle size of the nanoparticles was about 63.47 nm and the standard deviation was 0.61 nm.

[0053] Fig.16 Magnetic particle spectroscopy for quantifying the magnetic properties of the nanoparticles is shown. The nonlinear index of the nanoparticles synthesized according to "Condition E" shown in Table 4 was calculated to be 14.3731.

[0054] Fig.17 Magnetic particle spectroscopy for quantifying the magnetic properties of nanoparticles is shown. The nonlinear index of the nanoparticles synthesized according to "Condition E" shown in Table 4 was calculated to be 15.6437 after storage for about 1 month to examine the stability of the nanoparticles.

[0055] Fig.18 It was shown that after about 2 months of storage, as determined by dynamic light scattering, Fig.16 The average nanoparticle size of the nanoparticles was about 181.83 nm and the standard deviation was 1.0 nm.

[0056] Fig.19 Magnetic particle spectroscopy for quantifying the magnetic properties of nanoparticles is shown. The nonlinear index of the nanoparticles synthesized according to "Condition F" shown in Table 4 is 14.806.

[0057] Fig. 20 Magnetic particle spectroscopy is shown for quantifying the magnetic properties of nanoparticles. After approximately 1 month of storage, Fig.19 The nonlinear index of the nanoparticles was calculated to be 14.2168.

[0058] Fig.21 It was shown that after about 2 months of storage, as determined by dynamic light scattering, Fig.19 The average nanoparticle size of the nanoparticles was about 185.97 nm and the standard deviation was 0.25 nm.

[0059] Fig. 22 is a schematic diagram showing surface modification of example nanoparticles with amine groups for suspension stability and surface modification of example nanoparticles with polyethylene glycol-2000 (PEG-2000) for enhancing blood circulation. DETAILED DESCRIPTION

[0060] The magnetic nanoparticles described herein are found to be suitable for having tunable magnetic properties and surface functionalization. Provided herein are magnetic nanoparticles having these characteristics, methods for preparing these magnetic nanoparticles, and methods for treating, preventing, and / or imaging diseases in subjects in need thereof by administering these magnetic nanoparticles.

[0061] Nanoparticle composition

[0062] Provided herein are nanoparticle compositions comprising magnetic nanoparticles comprising ferric chloride, ferrous chloride, or a combination thereof, and a dextran coating. In some embodiments, the composition may comprise a mixture of two or more different nanoparticle compositions described herein. In some embodiments, the composition comprises at least one magnetic nanoparticle having tunable surface functionalization, and at least one magnetic nanoparticle having tunable magnetic properties.

[0063] Tunable amine functionalization

[0064] In some embodiments, the magnetic nanoparticles can be functionalized with one or more amine groups. In some embodiments, functionalization occurs on the surface of the magnetic nanoparticles. In some embodiments, one or more amine groups are covalently attached to the dextran coating. In some embodiments, one or more amine groups replace one or more hydroxyl groups of the dextran coating. In some embodiments, the number of one or more amine groups is tunable based on the concentration of ferric chloride, ferrous chloride, or a combination thereof. In some embodiments, the nanoparticle composition comprises about 5 to about 1000 amine groups. In some embodiments, the nanoparticle composition comprises about 5 to 25, 25 to 100, 100 to 150, 150 to 200, 200 to 250, 250 to 300, 300 to 350, 350 to 400, 450 to 500, 500 to 550, 550 to 600, 600 to 650, 650 to 700, 700 to 750, 750 to 800, 800 to 850, 850 to 900, 900 to 950, or 950 to 1000 amine groups.

[0065] In some embodiments, the magnetic nanoparticles may include a core of a magnetic material (e.g., ferric chloride and / or ferrous chloride). In some embodiments, the nanoparticle composition includes about 0.60 g to about 0.70 g of ferric chloride and about 0.3 g to about 0.5 g of ferrous chloride. In some embodiments, the nanoparticle composition comprising about 0.60 g to about 0.70 g of ferric chloride and about 0.3 g to about 0.5 g of ferrous chloride is functionalized with about 5 to 150 amine groups. In some embodiments, the nanoparticle composition comprising about 0.65 g of ferric chloride and about 0.4 g of ferrous chloride is functionalized with about 60 to 90 amine groups. In some embodiments, the nanoparticle composition comprising about 0.65 g of ferric chloride and about 0.4 g of ferrous chloride is functionalized with about 5 to 150 amine groups. In some embodiments, a nanoparticle composition comprising about 0.65 g of ferric chloride and about 0.4 g of ferrous chloride is functionalized with about 1 to 150 amine groups. In some embodiments, a nanoparticle composition comprising about 0.65 g of ferric chloride and about 0.4 g of ferrous chloride is functionalized with about at least 1 to 10 amine groups, 10 to 20 amine groups, about 20 to 30 amine groups, about 30 to 40 amine groups, about 40 to 50 amine groups, about 50 to 60 amine groups, about 60 to 70 amine groups, about 70 to 80 amine groups, about 80 to 90 amine groups, about 90 to 100 amine groups, about 100 to 110 amine groups, about 110 to 120 amine groups, about 120 to 130 amine groups, about 130 to 140 amine groups, or about 140 to 150 amine groups.

[0066] In some embodiments, the nanoparticle composition comprises about 1 g to about 1.4 g of ferric chloride. In some embodiments, the nanoparticle composition comprising about 1 g to about 1.4 g of ferric chloride is functionalized with about 246 to 500 amine groups. In some embodiments, the nanoparticle composition comprising about 1.2 g of ferric chloride is functionalized with about 246 to 500 amine groups. In some embodiments, the nanoparticle composition functionalized with about 246 to 500 amine groups does not comprise ferric chloride. In some embodiments, the nanoparticle composition comprising about 1.2 g of ferric chloride is functionalized with about 200 to 600 amine groups. In some embodiments, a nanoparticle composition comprising about 1.2 g of ferric chloride is functionalized with about at least 200 to 250 amine groups, 250 to 300 amine groups, about 300 to 350 amine groups, about 350 to 400 amine groups, about 400 to 450 amine groups, about 450 to 500 amine groups, about 500 to 550 amine groups, about 550 to 600 amine groups, or more.

[0067] Thus, in some embodiments, the number of amine groups conjugated to the dextran coating can be fine-tuned by controlling the concentration of ferric chloride and ferrous chloride used to prepare the magnetic nanoparticles.

[0068] Tunable magnetic

[0069] In some embodiments, the nanoparticle composition includes magnetic nanoparticles having a magnetic strength that is tunable based on the concentration of ferric chloride, ferrous chloride, or a combination thereof.

[0070] In some embodiments, the nanoparticle composition comprises about 0.1% to about 99.9% ferric ions and about 99.9% to about 0.1% ferrous ions of the total iron per MNP. In some embodiments, a nanoparticle composition comprising about 60% to about 80% ferric chloride and about 20% to about 40% ferrous chloride has a stronger magnetic property than a nanoparticle composition having an amount of ferrous chloride greater than about 80%. In some embodiments, a nanoparticle composition comprising about 70% ferric ions and about 30% ferrous ions has a stronger magnetic property than a nanoparticle composition having an amount of ferrous ions greater than about 30%.

[0071] In some embodiments, the magnetic strength of the magnetic nanoparticles can be quantified by determining the nonlinear index (NLI) by means of magnetic particle spectroscopy. The NLI is a criterion for determining whether a particle is suitable for magnetic particle imaging or other techniques that rely on the nonlinear behavior of magnetic nanoparticles. The NLI can be determined by calculating the ratio of F1 to F3, which are parameters in the magnetic particle spectrometer system. F1 / F3 compares the magnetization of the particle relative to the external magnetic field. F1 is the magnitude of the external magnetic excitation ("drive") frequency after Fourier decomposition, and F3 refers to the magnitude of the third harmonic of the drive frequency (for example, if the drive frequency is 25kHz, F1 is 25kHz and F3 is 75kHz); therefore, F1 and F3 are calculated using the magnitude of the frequency, and the process of Fourier decomposition allows the analysis of nonlinear correlations in the time domain. If the particle has a magnetic property that is linearly proportional to the external magnetic field used by the magnetic particle spectrometer, its nonlinear index will be very large. If the particle has a magnetic property that is linearly proportional to the external magnetic field used by the magnetic particle spectrometer, its nonlinear index will be very large. The magnetic permeability of particles without external magnetic field is relative to the magnetic intensity when magnetized with external magnetic field ( Fig. 9 , 11, 13, 14, 16, 17, 19, and 20) is larger, the smaller the nonlinear index will be (e.g., it will be closer to 1, the NLI of a square wave magnetization response). Conversely, the more similar the initial magnetic intensity of the particles is to their fully magnetized state, the larger the nonlinear index will be. Since the NLI is related to specific excitation conditions, the same external field (a sinusoidal field with a peak amplitude of 4.5 mT / μ0) was used in all measurements presented in this article, although the methods and analysis can be similarly applied to other operating conditions.

[0072] In some embodiments, the NLI of the nanoparticle composition ranges from about 6 to about 40. In some embodiments, the NLI of the nanoparticle composition ranges from about 6 to about 70. In some embodiments, the NLI of the nanoparticle composition ranges from about 8.5 to about 14.8. In some embodiments, the NLI of the nanoparticle composition ranges from about 8 to about 14. In some embodiments, the NLI of the nanoparticle composition is about 6. In some embodiments, the NLI of the nanoparticle composition is about 8. In some embodiments, the NLI of the nanoparticle composition is about 14. In some embodiments, the NLI of the nanoparticle composition is about 67. In some embodiments, the NLI of the nanoparticle composition ranges from 6 to 7, 7 to 8, 8 to 9, 9 to 10, 10 to 11, 11 to 12, 12 to 13, 13 to 14, 14 to 15, 15 to 16, 16 to 17, 17 to 18, 18 to 19, 19 to 20, 20 to 30, 30 to 40, 40 to 50, 50 to 60, or 60 to 70. In some embodiments, the nonlinear index of a nanoparticle composition comprising about 0.54 g of ferric chloride and about 0.2 g of ferrous chloride ranges from about 8.5 to about 14.8. In some embodiments, the nonlinear index of a nanoparticle composition comprising about 0.54 g of ferric chloride and about 0.2 g of ferrous chloride is about 12.

[0073] In some embodiments, the nanoparticle composition comprises about 80% to about 100% ferric chloride and about 20% to about 0% ferrous chloride. In some embodiments, a nanoparticle composition comprising about 0% to about 50% ferric chloride and about 100% to about 50% ferrous chloride has weaker magnetic properties than a nanoparticle composition having an amount of ferrous chloride less than about 0.4 g. In some embodiments, a nanoparticle composition comprising about 0.54 g ferric chloride and about 0.4 g ferrous chloride has weaker magnetic properties than a nanoparticle composition having an amount of ferrous chloride less than about 0.2 g.

[0074] In some embodiments, the nonlinear index of a nanoparticle composition comprising about 0.54 g of ferric chloride and about 0.4 g of ferrous chloride ranges from about 50 to about 120. In some embodiments, the nonlinear index of a nanoparticle composition comprising about 0.54 g of ferric chloride and about 0.4 g of ferrous chloride is about 67.

[0075] Thus, in some embodiments, the magnetic properties (eg, magnetic strength) of magnetic nanoparticles can be fine-tuned by controlling the concentration of ferric chloride and ferrous chloride used to prepare the magnetic nanoparticles.

[0076] In some embodiments, the iron concentration of the nanoparticle composition ranges from about 8 μM to about 217 μM. In some embodiments, the iron concentration of the nanoparticle composition ranges from about 8 μM to about 15 μM, about 15 μM to about 25 μM, about 25 μM to about 50 μM, 50 μM to about 60 μM, about 60 μM to about 70 μM, about 70 μM to about 80 μM, 80 μM to about 90 μM, about 90 μM to about 100 μM, about 100 μM to about 110 μM, 110 μM to about 120 μM. 0μM, about 120μM to about 130μM, about 130μM to about 140μM, 140μM to about 150μM, about 150μM to about 160μM, about 160μM to about 170μM, 170μM to about 180μM, about 180μM to about 190μM, about 190μM to about 200μM, 200μM to about 210μM, about 210μM to about 220μM.

[0077] In some embodiments, the nanoparticle composition has an iron concentration ranging from about 1 mg / mL to about 25 mg / mL. In some embodiments, the nanoparticle composition has an iron concentration ranging from about 1 mg / mL to about 5 mg / mL, about 5 mg / mL to about 10 mg / mL, about 10 mg / mL to about 15 mg / mL, about 15 mg / mL to about 20 mg / mL, or about 20 mg / mL to about 25 mg / mL.

[0078] Other physical properties

[0079] In some embodiments, the key properties of the nanoparticles for drug delivery include biodegradability, toxicity spectrum and pharmacokinetics / pharmacodynamics of the nanoparticles. The composition and / or size of the nanoparticles are the key determinants of their biological fate. For example, larger nanoparticles are usually taken up and degraded by the liver, while smaller nanoparticles (diameter < 30nm) usually circulate for a long time (sometimes exceeding 24 hours blood half-life in human body) and accumulate in the interstitium of lymph nodes and organs with high permeability vasculature such as tumors and metastases.

[0080] In some embodiments, the magnetic nanoparticles can have a diameter between about 2 nanometers (nm) and about 200 nm (e.g., between about 2 nm and about 10 nm, between about 10 nm and about 30 nm, between about 5 nm and about 25 nm, between about 10 nm and about 25 nm, between about 15 nm and about 25 nm, between about 20 nm and about 25 nm, between about 25 nm and about 50 nm, between about 50 nm and about 200 nm, between about 70 nm and about 200 nm). 120, 125, 140, or 150 nm, up to about 10, 20, 25, 30, 50, 75, 100, 150, 200, or 250 nm.

[0081] In some embodiments, provided herein is a magnetic nanoparticle that can be spherical or elliptical, or can have an amorphous shape. In some embodiments, provided herein is a magnetic nanoparticle that has a diameter (between any two points on the outer surface of a nanoparticle composition) that can be between about 2nm and about 200nm (for example, between about 10nm and about 200nm, between about 2nm and about 30nm, between about 5nm and about 25nm, between about 10nm and about 25nm, between about 15nm and about 25nm, between about 20nm and about 25nm, between about 50nm and about 200nm, between about 70nm and about 200nm, between about 80nm and about 200nm, between about 100nm and about 200nm, between about 140nm and about 200nm, and between about 150nm and about 200nm). In some embodiments, a magnetic nanoparticle with a diameter between about 2nm and about 30nm is concentrated (localized) to a tumor, lymph node, and metastatic lesions in a subject. In some embodiments, magnetic nanoparticles having a diameter between about 40 nm and about 200 nm localize to the liver.

[0082] In some embodiments, the magnetic nanoparticles provided herein may have a polydispersity index (PDI) of about 0.05 to about 0.25. PDI essentially represents the size population distribution within a given sample. The numerical value of PDI ranges from 0.0 (for a sample with completely uniform particle size) to 1.0 (for a highly polydisperse sample with multiple particle size populations). In some embodiments, the PDI of the magnetic nanoparticles provided herein can be about 0.050 to 0.100, about 0.100 to 0.110, about 0.110 to 0.120, about 0.120 to 0.130, about 0.130 to 0.140, about 0.140 to 0.150, about 0.150 to 0.160, about 0.160 to 0.170, about 0.170 to 0.180, about 0.180 to 0.190, about 0.190 to 0.200, about 0.200 to 0.210, about 0.210 to 0.220, about 0.230 to 0.240, or about 0.240 to 0.250.

[0083] In some embodiments, the magnetic material or particle can include a diamagnetic material, a paramagnetic material, a superparamagnetic material, or a ferromagnetic material that responds to a magnetic field. Non-limiting examples of therapeutic magnetic nanoparticles include a core of a magnetic material containing a metal oxide selected from the group consisting of: magnetite; ferrites (e.g., ferrites of manganese, cobalt, and nickel); Fe(II) oxides, and hematite, and metal alloys thereof. In some embodiments of the methods described herein, the location or positioning of the therapeutic magnetic nanoparticles can be imaged in a subject (e.g., imaging in a subject after administration of one or more doses of the magnetic nanoparticles).

[0084] Polymer coating

[0085] Magnetic nanoparticles as described herein include polymer (e.g., dextran) coating on nuclear magnetic material (e.g., on the surface of magnetic material).Polymer material can be suitable for attachment or coupling of one or more biological agents (e.g., nucleic acid as described herein).One or more biological agents (e.g., nucleic acid) can be attached to polymer coating by chemical coupling (e.g., covalent bond).

[0086] Methods for synthesizing iron oxide nanoparticles include, for example, physical methods and chemical methods. For example, iron oxide can be synthesized by Fe 2+ Salt and Fe 3+ The core is prepared by coprecipitation of a salt, for example, as described in Examples 1-8. The resulting core is composed of magnetite (Fe3O4), hematite (γ-Fe2O3), or a mixture of the two. The anion salt content (e.g., chloride, nitrate, sulfate, etc.) in the aqueous solution, Fe 2+ with Fe 3+The ratio of, pH, and ionic strength all play a role in the control of the size of the nanoparticles. It is important to prevent the oxidation of the synthesized nanoparticles and protect their magnetic properties by reacting in an oxygen-free environment under an inactive gas such as nitrogen or argon. Coating materials can be added during the coprecipitation process to prevent the iron oxide nanoparticles from aggregating into microparticles. Those skilled in the art will appreciate that any number of known surface coating materials can be used to stabilize the iron oxide nanoparticles, including synthetic and natural polymers, such as, for example, polyethylene glycol (PEG), dextran, polyvinyl pyrrolidone (PVP), fatty acids, polypeptides, chitosan, gelatin. In some embodiments, the nanoparticle composition comprises PEG. In some embodiments, the nanoparticle composition comprises PEG-2000. In some embodiments, the nanoparticle composition comprises PEG-1000, PEG-3000, PEG-3350, PEG-4000, PEG-6000, PEG-8000, PEG-12,000, PEG-20,000, or any combination thereof.

[0087] In some embodiments, the polymer coating is dextran. In some embodiments, the dextran coating is covalently attached to the magnetic nanoparticles. In some embodiments, the dextran coating comprises a dextran with a molecular weight range of about 1 kilodalton (kDa) to about 15kDa. In some embodiments, the dextran coating comprises a dextran with a molecular weight of about 1kDa. In some embodiments, the dextran coating comprises a dextran with a molecular weight of about 5kDa. In some embodiments, the dextran coating comprises a dextran with a molecular weight of about 10kDa. In some embodiments, the dextran coating comprises a dextran with a molecular weight of about 15kDa. In some embodiments, the dextran coating comprises a chemically cross-linked dextran, as described in Example 2. Optional suitable polymers that can be used to coat the core of the magnetic material include but are not limited to: polystyrene, polyacrylamide, polyetherurethane (polyetherurethane), polysulfone, fluorinated or chlorinated polymers such as polyvinyl chloride, polyethylene and polypropylene, polycarbonate and polyester. Other examples of polymers that can be used to coat the core of the magnetic material include polyolefins, such as polybutadiene, polydichloroprene, polyisoprene, polychloroprene, polyvinylidene halide, polyvinylidene carbonate, and polyvinylidene fluoride. Many copolymers including styrene / butadiene, α-methylstyrene / dimethylsiloxane, or other polysiloxanes can also be used to coat the core of the magnetic material (e.g., polydimethylsiloxane, polyphenylmethylsiloxane, and polytrifluoropropylmethylsiloxane). Other polymers that can be used to coat the core of the magnetic material include polyacrylonitrile or acrylonitrile-containing polymers, such as poly-α-acrylonitrile copolymers, alkyd resins or terpenoid resins, and polyalkylenepolysulfonates.

[0088] Drug payload

[0089] In some embodiments, the nanoparticle composition further comprises a drug payload. In some embodiments, the drug payload can be attached (e.g., by covalent bonding) to the surface of the dextran coating. In some embodiments, the drug payload is a drug, an antibody, a growth factor, a nucleic acid, a nucleic acid derivative, a nucleic acid fragment, a protein, a protein derivative, a protein fragment, a peptide, a small molecule, or any combination thereof. In some embodiments, the drug payload is an oligonucleotide conjugated to one or more amine groups of a polymer coating (e.g., a dextran coating). In some embodiments, the drug payload is a nucleic acid. In some embodiments, the nucleic acid is single-stranded or double-stranded. In some embodiments, the nucleic acid is an antisense RNA, a small interfering RNA (siRNA), a DNA, a microRNA mimic, an aptamer, or a nuclease. In some embodiments, the nucleic acid molecule may include at least one modified nucleotide (containing a modified base or sugar nucleotide). In some embodiments, the nucleic acid molecule may include at least one modification in a phosphate (phosphodiester) backbone. Introducing these modifications can increase the stability of the nucleic acid molecule or improve the hybridization or solubility of the nucleic acid molecule.

[0090] In some embodiments, the drug payload (e.g., nucleic acid) is attached to the magnetic nanoparticle (e.g., attached to the polymer coating of the magnetic nanoparticle) via a chemical moiety containing a thioether bond or a disulfide bond. In some embodiments, the nucleic acid is attached to the magnetic nanoparticle via a chemical moiety containing an amide bond. Other chemical moieties that can be used to covalently link nucleic acids to magnetic nanoparticles are known in the art.

[0091] A variety of different methods can be used to covalently link the drug payload to the magnetic nanoparticles. In some embodiments, carbodiimides are used to attach the drug payload to the magnetic nanoparticles.

[0092] Pharmaceutical composition

[0093] Also provided herein is a pharmaceutical composition comprising any nanoparticle composition of the present disclosure and at least one pharmaceutically acceptable carrier or diluent. In some embodiments, the pharmaceutical composition comprises magnetic nanoparticles as described herein. Two or more (e.g., two, three, or four) magnetic nanoparticles of any type described herein may be present in the pharmaceutical composition in any combination. The pharmaceutical composition may be formulated in any manner known in the art.

[0094] The pharmaceutical composition is formulated to be compatible with its expected route of administration (e.g., intravenous, intra-arterial, intramuscular, intradermal, subcutaneous, or intraperitoneal). The composition may include a sterile diluent (e.g., sterile water or saline), a fixed oil, polyethylene glycol, glycerol, propylene glycol or other synthetic solvents, antibacterial or antifungal agents such as benzyl alcohol or methyl paraben, chlorobutanol, phenol, ascorbic acid, and thimerosal, etc., antioxidants such as ascorbic acid or sodium bisulfate, chelating agents such as ethylenediaminetetraacetic acid, buffers such as acetates, citrates, or phosphates, and isotonic agents such as sugars (e.g., glucose), polyols (e.g., mannitol or sorbitol), or salts (e.g., sodium chloride), or any combination thereof. Liposomal suspensions may also be used as pharmaceutically acceptable carriers. The preparation of the composition may be prepared and packaged in an ampoule, a disposable syringe, or a multiple dose bottle. As required (as in, for example, injectable preparations), suitable fluidity can be maintained by, for example, using coatings such as lecithin or surfactants. The absorption of nanoparticle compositions can be extended by comprising an agent (for example, aluminum monostearate and gelatin) that delays absorption. Alternatively, controlled release can be achieved by implants and microencapsulated delivery systems, which can include biodegradable biocompatible polymers (for example, ethylene vinyl acetate, polyanhydrides, polyglycolic acid, collagen, polyorthoesters, and polylactic acid). Compositions comprising one or more of any magnetic nanoparticles described herein can be formulated in dosage unit form (that is, physically discrete units containing a predetermined amount of active compound for ease of use and uniform dosage) for parenteral (for example, intravenous, intraarterial, intramuscular, intradermal, subcutaneous, or intraperitoneal) administration.

[0095] The toxicity and therapeutic efficacy of the composition can be determined by standard pharmaceutical procedures in cell culture or experimental animals (e.g., monkeys). The LD50 (the dose that is lethal to 50% of the population) and the ED50 (the dose that is therapeutically effective in 50% of the population) can be determined, for example: the therapeutic index is the ratio of LD50:ED50. Agents that exhibit high therapeutic indices are preferred. When an agent exhibits undesirable side effects, care should be taken to minimize potential damage (i.e., reduce undesirable side effects). Toxicity and therapeutic efficacy can be determined by other standard pharmaceutical procedures.

[0096] The data obtained from cell culture analysis and animal studies can be used to formulate any given medicament for the appropriate dose of a subject (e.g., a human). The therapeutically effective amount of one or more (e.g., one, two, three, or four) magnetic nanoparticles (e.g., any magnetic nanoparticles described herein) will be an amount that reduces cancer cell invasion or metastasis in a subject with cancer, treats metastatic cancer in a subject, reduces or stabilizes the size of metastatic tumors in a subject, reduces the growth rate of metastatic tumors in a subject, reduces the severity, frequency, and / or duration of one or more symptoms of metastatic cancer in a subject (e.g., a human), or reduces the number of symptoms of metastatic cancer in a subject (e.g., compared to a control subject with the same disease but not receiving treatment or receiving a different treatment, or compared to the same subject before treatment).

[0097] The effectiveness and dosage of any magnetic composition described herein can be determined by a medical professional using methods known in the art, and by observing one or more symptoms of metastatic cancer in a subject (e.g., a human). Certain factors may affect the dosage and timing required to effectively treat a subject (e.g., the severity of the disease or condition, previous treatment, the general health and / or age of the subject, and the presence of other diseases).

[0098] Exemplary dosages include any nanoparticle composition described herein in milligrams or micrograms per kilogram of subject body weight. Although these dosages cover a wide range, it will be appreciated by those of ordinary skill in the art that the therapeutic agents comprising the nanoparticle compositions described herein have different efficacy, and the effective amount can be determined by methods known in the art. Typically, a relatively low dose is first administered, and the attending medical professional (in the case of therapeutic applications) or researcher (when still in the development stage) can then gradually increase the dose until an appropriate response is obtained. In addition, it should be understood that the specific dosage level for any particular subject will depend on various factors, including the activity of the specific compound employed, the subject's age, weight, general health, sex and diet, time of administration, route of administration, excretion rate, and the half-life of the nanoparticle composition in vivo.

[0099] The pharmaceutical compositions can be included in a container, pack, or dispenser together with instructions for administration.

[0100] Synthesis method

[0101] In some embodiments, provided herein are methods of preparing any of the nanoparticle compositions disclosed herein, as described in detail in Examples 1-8. In some embodiments, the method comprises dissolving dextran in water, preparing a ferrous chloride solution, a ferric chloride solution, or a combination thereof. In some embodiments, the method comprises preparing a mixture by adding a ferrous chloride solution, a ferric chloride solution, or a combination thereof to the dextran.

[0102] In some embodiments, the method includes adding a base to the mixture while stirring and subjecting the mixture to an ice bath. In some embodiments, the method includes adding about 10mL to 15mL of base to the mixture. In some embodiments, the method includes adding about 25mL to 30mL of base to the mixture. In some embodiments, the method includes adding at least about 10mL to 15mL, 15mL to 20mL, 20mL to 25mL, 25mL to 30mL or more of base to the mixture. In some embodiments, the base is ammonium hydroxide. In some embodiments, the base is sodium hydroxide. In some embodiments, the method includes adding about 10mL of ammonium hydroxide to the mixture. In some embodiments, the method includes adding about 15mL of ammonium hydroxide to the mixture. In some embodiments, the method includes adding about 25mL of ammonium hydroxide to the mixture. In some embodiments, the method includes adding about 30mL of ammonium hydroxide to the mixture.

[0103] In some embodiments, the method includes adding ammonium hydroxide to the mixture while stirring and subjecting the mixture to an ice bath. In some embodiments, an excess of ammonia or ammonium hydroxide is required to introduce an amine group at the same site of a hydroxyl group on the dextran coating. In some embodiments, the method includes adding about 60 mL of ammonium hydroxide to the mixture (e.g., a nanoparticle precursor composition). In some embodiments, the method includes subjecting the mixture to a temperature of about 75 ° C to about 90 ° C. In some embodiments, the method includes subjecting the mixture to a temperature of about 75 ° C to about 90 ° C after adding ammonium hydroxide. In some embodiments, the step of adding ammonium hydroxide prevents the formation of iron oxide crystals, iron oxide hydrates, or a combination thereof. In some embodiments, the step of adding ammonium hydroxide functionalizes the dextran coating with one or more amine groups.

[0104] In some embodiments, the method includes cross-linking the dextran with epichlorohydrin. Epichlorohydrin is a chemical substance that can be used to cross-link two hydroxyls on the dextran polymer backbone. In some embodiments, cross-linking with epichlorohydrin ensures the chemical stability of the dextran coating on the surface of the iron oxide core. In some embodiments, epichlorohydrin can be polymerized to extend the hydroxyl chain on the dextran polymer backbone, which can cause the increase of hydroxyls that can be substituted by amine groups. In some embodiments, ammonium hydroxide is added to the mixture to destroy the remaining unreacted epichlorohydrin in the reaction mixture.

[0105] In some embodiments, any nanoparticle composition of the present disclosure can be amplified. For example, in some embodiments, the method further includes producing a first nanoparticle composition of the first final volume of about 21 mL. In some embodiments, the first nanoparticle composition (for example, a small-scale batch of magnetic nanoparticles) includes a first magnetic nanoparticle, characterized in that it has a first set of physical properties. In some embodiments, the method further includes producing a second nanoparticle composition (for example, a large-scale batch of magnetic nanoparticles) of at least a second final volume greater than about 21 mL. In some embodiments, the second final volume of the second nanoparticle composition is about 20 mL to about 30 mL, about 30 mL to about 40 mL, about 40 mL to about 50 mL, about 50 mL to about 60 mL, about 60 mL to about 70 mL, about 70 mL to about 80 mL, about 80 mL to about 90 mL, about 90 mL to about 100 mL, about 100 mL to about 100 mL, or about 110 mL to about 120 mL.

[0106] In some embodiments, the second nanoparticle composition includes a second magnetic nanoparticle characterized by having a second set of physical properties. In some embodiments, the first set of physical properties and the second set of physical properties are substantially the same. In some embodiments, any nanoparticle composition of the present disclosure can be amplified without changing its physical properties (e.g., size, PDI, or NLI). In some embodiments, any nanoparticle composition of the present disclosure can be amplified without changing its physical properties. In some embodiments, the first physical property and the second physical property include diameter, magnetic intensity, polydispersity index, surface charge, nonlinear index value, PDI value, or any combination thereof.

[0107] In some embodiments, the nanoparticle compositions disclosed herein are stable for at least about 1 day to about 6 months or more. As used herein, the term "stable" or "stability" means that any physical properties of the same sample of the magnetic nanoparticles or compositions are not changed as measured and compared from the day the magnetic nanoparticles or compositions are prepared to the day they are stored as samples. In some embodiments, the nanoparticle compositions disclosed herein are stable for at least about 1 day to about 5 days, about 5 days to 10 days, about 10 days to about 15 days, about 15 days to 30 days, about 30 days to about 40 days, about 40 days to 50 days, about 50 days to about 60 days, about 3 months to about 4 months, about 4 months to about 5 months, about 5 months to about 6 months, or longer.

[0108] Treatment

[0109] In some embodiments, provided herein are methods for treating a disease, preventing a disease, or imaging a disease in a subject in need. In some embodiments, the method comprises administering a therapeutically effective amount of any nanoparticle composition disclosed herein to at least one target site at a portion of a subject's body, body part, tissue, cell, or body fluid. In some embodiments, any nanoparticle composition of the present disclosure is used for a method of treating a disease in a subject in need. In some embodiments, any nanoparticle composition of the present disclosure is used for a method of imaging a disease (e.g., by magnetic resonance imaging (MRI)) in a subject in need. In some embodiments, provided herein are methods for reducing (e.g., significantly or observably reducing) cancer cell invasion or metastasis in a subject. In some embodiments, the method comprises administering to a subject at least one nanoparticle composition described herein in an amount sufficient to reduce cancer cell invasion or metastasis in a subject.

[0110] In some embodiments, the method further includes applying energy to the magnetic nanoparticle composition and the target site. In some embodiments, the energy is light energy or magnetic energy. For example, in some embodiments, the step of applying energy may include applying a magnetic field or exposing the subject to which any nanoparticle composition described herein has been applied to a magnetic field for magnetic resonance imaging. In some embodiments, the nanoparticle composition is used to image a part of the subject's body, body part, tissue, cell, or body fluid. In some embodiments, the nanoparticle composition can treat a disease, prevent a disease (for example, by being able to detect an early stage cancer to prevent further metastasis of cancer cells) and / or image a disease. In some embodiments, the disease is cancer. In some embodiments, the disease is metastatic cancer.

[0111] In some embodiments, the target site is a tumor site. In some embodiments, the nanoparticle composition accumulates at the target site of the subject (e.g., due to the size of the magnetic nanoparticles disclosed herein). In some embodiments, the method further comprises imaging the target site using the nanoparticle composition. In some embodiments, magnetic resonance imaging is used for imaging.

[0112] In some embodiments, the step of applying energy to the magnetic nanoparticle composition and the target site is an optional step. For example, the magnetic composition can be used alone as a therapeutic composition, rather than being used as a therapeutic composition and an imaging agent (e.g., a contrast agent) at the same time. In some embodiments, the magnetic composition is used alone as an imaging agent (e.g., a contrast agent), rather than being used as a therapeutic composition and an imaging agent at the same time.

[0113] Dosage, Administration and Composition

[0114] In any of the methods described herein, the nanoparticle compositions can be administered by a healthcare professional (e.g., a physician, a physician's assistant, a nurse, or a laboratory or clinical staff), a subject (i.e., self-administration). Administration can be performed in a clinical setting (e.g., in a clinic or hospital), in an assisted living facility, or in a pharmacy.

[0115] In some embodiments of any method described herein, the nanoparticle composition is administered to a subject diagnosed with a disease (e.g., cancer such as primary cancer or metastatic cancer). In some embodiments, the subject has been diagnosed with metastatic cancer. Non-limiting examples of metastatic cancer include breast cancer, bladder cancer, colon cancer, kidney cancer, lung cancer, melanoma, ovarian cancer, pancreatic cancer, prostate cancer, rectal cancer, gastric cancer, thyroid cancer, and uterine cancer. In some non-limiting embodiments, the subject is male or female, adult, adolescent, or child. The subject may have experienced one or more symptoms of cancer or metastatic cancer (e.g., metastatic cancer in lymph nodes). The subject may also be diagnosed as suffering from severe or advanced cancer (e.g., primary cancer or metastatic cancer). In some embodiments, the subject may be identified as suffering from a metastatic tumor present in at least one lymph node. In some embodiments, the subject may have undergone lymph node resection and / or mastectomy.

[0116] In some embodiments of any of the methods described herein, at least one (e.g., at least 2, 3, 4, 5, 6, 7, 8, 9, 10, 15, 20, 25, or 30) doses of a composition containing at least one (e.g., one, two, three, or four) of any nanoparticle composition or pharmaceutical composition described herein is administered to a subject. In any of the methods described herein, at least one nanoparticle composition or pharmaceutical composition (e.g., any nanoparticle composition or pharmaceutical composition described herein) can be administered intravenously, intraarterially, subcutaneously, intraperitoneally, or intramuscularly to a subject. In some embodiments, at least the magnetic particles or pharmaceutical composition are administered (injected) directly into a lymph node of a subject.

[0117] In some embodiments, at least one nanoparticle composition or pharmaceutical composition (e.g., any nanoparticle composition or pharmaceutical composition described herein) and at least one additional therapeutic agent are administered to a subject. The at least one additional therapeutic agent can be a chemotherapeutic agent (e.g., cyclophosphamide, mechlorethamine, chlorambucil, melphalan, daunorubicin, doxorubicin, epirubicin, idarubicin, mitoxantrone, valrubicin, paclitaxel, docetaxel, etoposide, teniposide, tafluposide, azacitidine). , azathioprine, capecitabine, cytarabine, doxifluridine, fluorouracil, gemcitabine, mercaptopurine, methotrexate, tioguanine, bleomycin, carboplatin, cisplatin, oxaliplatin, bortezomib, carfilzomib, salinosporamide A, all-trans retinoic acid, vinblastine, vincristine, vindesine, and vinorelbine) and / or analgesics (e.g.,Acetaminophen, diclofenac, diflunisal, etodolac, fenoprofen, flurbiprofen, ibuprofen, indomethacin, ketoprofen, ketorolac, meclofenamate, mefenamic acid, meloxicam, nabumetone, naproxen, oxaprozin, phenylbutazone, piroxicam roxicam, sulindac, tolmetin, celecoxib, buprenorphine, butorphanol, codeine, hydrocodone, hydromorphone, levorphanol, meperidine, methadone, morphine, nalbuphine, oxycodone, oxymorphone, pentazocine, propoxyphene, and tramadol).

[0118] In some embodiments, at least one additional therapeutic agent and at least one magnetic nanoparticle (e.g., any nanoparticle composition described herein) are administered in the same composition (e.g., the same pharmaceutical composition). In some embodiments, at least one additional therapeutic agent and at least one magnetic nanoparticle are administered to a subject using different routes of administration (e.g., at least one additional therapeutic agent is delivered by oral administration and at least one magnetic nanoparticle is delivered by intravenous administration).

[0119] In any of the methods described herein, at least one nanoparticle composition or pharmaceutical composition (e.g., any nanoparticle composition or pharmaceutical composition described herein) and optionally at least one additional therapeutic agent can be administered to a subject at least once a week (e.g., once a week, twice a week, three times a week, four times a week, once a day, twice a day, or three times a day). In some embodiments, at least two different nanoparticle compositions are administered in the same composition (e.g., a liquid composition). In some embodiments, at least one nanoparticle composition and at least one additional therapeutic agent are administered in the same composition (e.g., a liquid composition containing at least one nanoparticle composition and a solid oral composition containing at least one additional therapeutic agent). In some embodiments, at least one additional therapeutic agent is administered in a pill, tablet, or capsule.

[0120] In some embodiments, at least one additional therapeutic agent is administered in a sustained-release oral formulation. In some embodiments, one or more additional therapeutic agents may be administered to a subject before administering at least one nanoparticle composition or pharmaceutical composition (e.g., any nanoparticle composition or pharmaceutical composition described herein). In some embodiments, one or more additional therapeutic agents may be administered to a subject after administering at least one nanoparticle composition or pharmaceutical composition (e.g., any magnetic particle or pharmaceutical composition described herein). In some embodiments, one or more additional therapeutic agents and at least one nanoparticle composition or pharmaceutical composition (e.g., any nanoparticle composition or pharmaceutical composition described herein) are administered to a subject so that there is overlap in the biologically active period of one or more additional therapeutic agents and at least one nanoparticle composition (e.g., any nanoparticle composition described herein) in the subject.

[0121] In some embodiments, at least one nanoparticle composition or pharmaceutical composition (e.g., any nanoparticle composition or pharmaceutical composition described herein) can be administered to a subject over an extended period of time (e.g., over a period of at least one week, two weeks, three weeks, one month, two months, three months, four months, five months, six months, seven months, eight months, nine months, ten months, eleven months, twelve months, one year, two years, three years, four years, five years, or ten years). A skilled medical professional can determine the length of the treatment period using any of the methods described herein for diagnosing or tracking the effectiveness of a treatment (e.g., using the methods described above and methods known in the art). As described herein, based on the evaluation of the effectiveness of the treatment (e.g., using any of the methods described herein and known in the art), a skilled medical professional can also change the identity and amount (e.g., increase or decrease) of the nanoparticle composition (and / or one or more additional therapeutic agents) administered to the subject, and can also adjust (e.g., increase or decrease) the dose and frequency of administering at least one nanoparticle composition (and / or one or more additional therapeutic agents) to the subject. A skilled medical professional can further determine when to discontinue treatment (such as, for example, when the subject's symptoms are significantly reduced).

[0122] Example

[0123] Certain embodiments of the present disclosure are further described in the following examples, which do not limit the scope of any embodiments described in the claims.

[0124] Example 1 - Synthesis of Magnetic Nanoparticles (MN) with Modular Amine-Based Payloads

[0125] The synthesis of magnetic nanoparticles (MN) was performed using an exemplary apparatus comprising a glass plate, ice, comprising a round bottom flask. The round bottom flask contained the reaction components described further below. The round bottom flask was placed on a hot plate / stir plate.

[0126] The formulation of MN included dextran (9 g / 30 mL DI water), 0.65 g ferric chloride, 0.4 g ferrous chloride, and 15 mL NH4OH (28%).

[0127] First, 9 grams of dextran T10 was dissolved in deionized water (DI water) to reach 30 mL (30% w / v) in a conical tube. Dextran T10 (technical quality) is a high-purity dextran fraction with an average molecular weight of 10 kDa. When the solution forms a precipitate at room temperature within three days, a fresh dextran solution was prepared.

[0128] Then, the dextran is dissolved in deionized (DI) water on a rotator at room temperature for 1 hour. The resulting solution is colorless, but it may appear slightly turbid with bubbles. Moderate heat may be applied to completely dissolve the dextran. An example of an apparatus for dextran dissolution is shown in Figure 1 .

[0129] The dextran solution was filtered into a 250 mL round bottom flask containing a magnetic stir bar using a 0.2 micron (μm) / 0.45 μm filter. Any remaining dextran in the tube can be rinsed with distilled water as needed. The dissolved solution in the two-necked round bottom flask (RBF) was cooled in an ice bath for 30 minutes with gentle magnetic stirring and nitrogen (or argon) bubbling (not air purging) to remove dissolved oxygen.

[0130] Then, prepare a ferric chloride stock solution. The amount of ferric chloride used for "Condition 1" is 0.65g of ferric chloride hexahydrate (FeCl3·6H2O), and 1.2g of ferric chloride hexahydrate (FeCl3·6H2O) is used for "Condition 2". The salt is dissolved in about 5mL of DI water, as shown in Table 1. The stock solution is brown, filtered using a 0.22μM filter unit, and stored in a cold, dark place. The amount of iron is calculated by subtracting the other elements in the iron salt composition. The ferrous chloride tetrahydrate bottle is stored in a desiccator to minimize oxidation by air. Powdered ferrous chloride should be green, and the formation of brown crystals in the bottle is an indication of iron oxidation (i.e., conversion from Fe(II) to Fe(III)), which should be avoided in order to obtain high-quality superparamagnetic nanoparticles.

[0131] Then, prepare ferrous chloride solution (FeCl2 · 4H2O).Freshly weigh 0.4 gr of ferrous chloride (condition 1) and dissolve in 1 mL of DI water in an Eppendorf tube to produce a pearlescent blue-green solution.0.0 gr of ferrous chloride is used for the recipe of condition 2.To dissolve ferrous chloride, DI water is purged with nitrogen for 10 minutes (min) to remove dissolved oxygen in the water.No filtration is required after dissolution, but the dissolution step is carried out for 15 minutes (for 0.4 g of ferrous chloride - i.e. condition 1) to ensure complete dissolution.The amount of iron is calculated by ignoring other elements in the iron salt composition.

[0132] 0.65 g of ferric chloride in 1 mL of ferric chloride stock solution (condition 1) and 1.2 g of ferric chloride in 2-5 mL of ferric chloride stock solution (condition 2) were added to the cold dextran solution. The mixture was stirred in a flask under continuous nitrogen (or argon) bubbling for 1 hour. After 30 minutes, 1 mL of ferrous chloride solution (0.4 g FeCl2 (condition 1) or (0.0 g FeCl2 (condition 2) was added to the flask as shown in Table 1. All necks of the Rbf were covered with rubber stoppers to prevent oxidation by minimizing air contact, but one neck had a gas outlet with a needle (18G) at the top of the rubber stopper.

[0133] Table 1 - Formulations of magnetic nanoparticles (MN) with modular amine-based payloads

[0134] Condition 1 Condition 2 <![CDATA[FeCl3·6H2O (Iron(III) chloride hexahydrate)]]> 0.65g 1.2g <![CDATA[(FeCl2·4H2O) (Iron(II) chloride tetrahydrate)]]> 0.4g 0g Total iron salts added 1.05g 1.2g Total Iron (Fe) Added 240mg 240mg

[0135] The reaction mixture is then titrated slowly. If ammonium hydroxide is added slowly, the viscosity increases, thereby interfering with the uniform mixing of ammonium hydroxide in the ferric iron / ferrous iron mixture, producing large particles.

[0136] In ice bath, continue to stir vigorously for 30 minutes.Keep the ice bath below the reaction mixture, and keep stirring during the whole process.After 60 minutes, one neck is connected to a water-cooled condenser, and another neck is connected to an inert gas to purge (not in the reaction mixture) under high heat. Be careful to avoid causing violent boiling at high temperature. Reaction Rbf is placed in an oil bath preheated to 90 ℃ again.Stirring is continued in oil bath for 90 minutes.Thermometer is maintained in the reaction mixture to measure temperature, and the temperature is maintained at at least about 75 ℃ to 85 ℃.After this step, stop airflow, and the solution is slowly cooled to room temperature.Realize the formation of the magnetic nanoparticles of dextran coating at the end of this series of reactions.The volume of final solution is about 40mL.

[0137] The resulting solution was purified by Amicon tubes (50K centrifugal filter units) to remove unreacted dextran, iron salts, and ammonium hydroxide. The nanoparticle suspension was first concentrated by centrifugation (~1,500×g (RCF) 3-4k RPM, 30 to 45 minutes), which resulted in a highly concentrated nanoparticle suspension on the filter and a nanoparticle-free eluate below the filter unit. The eluate below the filter was discarded, the nanoparticle pellet was resuspended in DI water, and the same filter unit was used for centrifugation again. This step was repeated until the eluate showed a pH of DI water or a neutral pH. Initially, due to the viscosity of the solution in the mixture, large-sized particulate impurities, and a large amount of unreacted free dextran, centrifugation took about 1 hour. However, after the first 3 or 4 centrifugation steps, most of the free dextran was removed, and the resuspension and concentration of the nanoparticles were completed in relatively short centrifugation steps (about 15 minutes per centrifugation step). The washing step was repeated 7 times. The resulting purified solution of magnetic nanoparticles was resuspended in distilled water. The final volume was adjusted to 21 mL, and the solution was placed in a refrigerator (eg, at about 4° C.) overnight.

[0138] Example 2 - Crosslinking and amination

[0139] Nanoparticles are crosslinked and aminated using sodium hydroxide, epichlorohydrin, and ammonium hydroxide through a series of reaction steps. 21 mL of MN is mixed with 35 mL of sodium hydroxide (NaOH), 14 mL of epichlorohydrin + 60 mL of ammonium hydroxide (NH4OH). The experiment is carried out in a fume hood, and safety precautions are taken to minimize exposure to the chemicals used in the synthesis. 35 mL of NaOH (5M) is stored at 4 ° C. In order to prepare 5M NaOH solution from pellets (ACROS 134070010, 1 kg, CAS 1310-732), 200 g is weighed and added to a glass bottle. 1 L of water (milllipore) is added to the bottle, the bottle cap is covered, and the mixture is vortexed.

[0140] Cold 35mL of NaOH (5M) was added to the cold 21mL of nanoparticle suspension in a 250mL round-bottom flask in an ice bath. The reaction mixture was stirred for 15 minutes in an ice bath without airflow. 14mL of epichlorohydrin was added to the reaction mixture with vigorous stirring. After adding epichlorohydrin, the resulting solution formed two liquid phases. After mixing, the temperature was maintained at room temperature. The cross-linking reaction was continued for 8 hours at room temperature with vigorous stirring. The cross-linking reaction was exothermic, and the temperature was monitored and controlled so that it did not exceed 35°C.

[0141] Epichlorohydrin was used to crosslink two hydroxyl groups on the dextran polymer backbone. Crosslinking with epichlorohydrin ensures chemical stability of the dextran coating on the surface of the iron oxide core of the MN. Epichlorohydrin can be polymerized to extend the chain, which can lead to an increase in hydroxyl groups to be subsequently substituted by amines.

[0142] The resulting homogeneous solution was then reacted with ammonium hydroxide to aminize the final nanoparticle composition. For both Condition 1 and Condition 2, 60 mL of ammonium hydroxide (NH4OH, 28%) was added to the reaction mixture. The reaction mixture was stirred at room temperature for 48 hours. The neck of the round-bottom flask was covered with a rubber stopper to prevent ammonia evaporation, which is important for obtaining a high amination yield. After the reaction was completed, the solution (~150 mL) was transferred to a dialysis bag (MWCO 12-14 kDa) and dialyzed with 4-6 L of distilled water in a beaker in a fume hood with continuous stirring. The dialysis was repeated several times over two days to remove all unreacted ammonium hydroxide and by-products (6-7 times). Continue until the ammonia smell in the dialysis bag disappears and the pH is neutral. Thereafter, repeat 3-4 more times. An example of a dialysis device is Figure 2 shown.

[0143] Then, the obtained brown-black nanoparticle suspension was concentrated to 20 mL using an Amicon centrifugal unit (MWCO 30 kDa, 2.8 k rpm, 15 min). The concentrated nanoparticles were suspended in 100 mM PBS buffer (pH 7.4). The solution was washed once again with PBS buffer using an Amicon centrifugal unit (MWCO 30 kDa, 2.8 k turns per minute (RPM), 15 minutes). The volume was adjusted to 15 mL using PBS buffer (pH 7.4). The nanoparticle solution was centrifuged at 14500 rpm. Then, large particles were filtered out using a 0.1 μM filter unit. Iron analysis was performed to determine the amount of iron in the solution. The volume was adjusted to 12 mg Fe / mL using PBS buffer (pH = 7.4). The size of the nanoparticles (approximately 22 ± 3 nm in diameter) was determined using a Nanosizer by dynamic light scattering.

[0144] Example 3 - Characterization of Iron Concentration of MN

[0145] The iron content was determined by performing the iron analysis described below and used to calculate the nanoparticle concentration. The amount of iron was determined using 8 standard iron solutions and 4 samples using the iron analysis described below. 10 μL of the iron standard and the nanoparticle solution were added to 980 μL of 6N HCl. 10 μL of hydrogen peroxide (H2O2, 30% in H2O) was added to each mixture. A blank sample was prepared by adding 10 μL of distilled water to 980 μL of 6N HCl and 10 μL of H2O2 instead of the iron standard. The iron oxide cores were digested during this process. The optical density (OD) at 410 nm was measured by UV-vis spectroscopy. A calibration curve was obtained using the standards. The concentration of the iron content in the nanoparticle solution was determined using the obtained calibration curve. An example of a UV-Vis curve is shown in Figure 3 In previous experiments, concentrations between 8.7 μM (ie, 1 mg / mL) of iron and 216.9 μM (ie, 25 mg / mL) of iron were found.

[0146] SPDP Quantification

[0147] 725 μl of water was added to 25 μl of conjugated nanoparticles. Two identical tubes of dilution were prepared (i.e., with or without TCEP digestion). 25 μl of 3% TCEP was added. The solution was incubated at room temperature for about 10 minutes. The solution was then filtered through a small Amicon filter (Eppendorf type; 100k cut off). The solution was then centrifuged at 7000 RPM for about 2-5 minutes. The absorbance of the filtrate was measured at 343 nm. The absorbance data measured at 343 nm for the filtrate with TCEP was approximately 0.33, and no peak was found in the filtrate without TCEP treatment. The total number of SPDPs per nanoparticle was calculated as follows. Total number of SPDPs: 0.33×10 6×30 (dilution factor) / 8100 (extinction coefficient) = 1200. Since the nanoparticle concentration was 20 μM (2.2 mg / mL), the number of SPDP per nanoparticle was calculated by dividing 1200 SPDP by 10 μM and yielded 60 SPDP / μM NP.

[0148] Example 4 - Characterization of Nanoparticle Size and Amine Content

[0149] Dynamic light scattering was used to determine the nanoparticle size. In previous experiments, nanoparticles with radii as large as about 20 to 35 nm and as small as about 11.5 to 15.6 nm were synthesized, as Figure 4 and 5 shown.

[0150] The amine content was quantified by the amount of SPDP (3-(2-pyridyldithio) propionic acid N-succinimidyl ester) conjugated to the nanoparticles. SPDP is a heterobifunctional linker reactive toward amino and sulfhydryl groups. SPDP-functionalized nanoparticles were cleaved with the aid of a reducing agent (3% TCEP) to release a detectable pyridine-2-thione (P2T) byproduct. Quantification of P2T was achieved by monitoring the maximum absorption peak at 343 nm (extinction coefficient at 343 nm was 8.08×10 3 / cm / M). The number of P2T gives the number of reactive amine groups in the solution. Therefore, the number of amine groups per nanoparticle is calculated by the concentration ratio of P2T to nanoparticles.

[0151] Briefly, a portion of the nanoparticle suspension (100 μL) was diluted in 800 μL of phosphate buffered saline (PBS, pH 7.4). The SPDP bottle was taken out of the refrigerator and equilibrated to room temperature before opening to avoid moisture accumulation in the bottle. This is important to prevent hydrolysis of the NHS ester of SPDP. A 100 mM SPDP stock solution was prepared in anhydrous DMSO. SPDP has limited water solubility, therefore, the nanoparticle solution was slowly titrated into the SPDP solution (in DMSO) to prevent SPDP crystallization. 100 μl of nanoparticles was diluted with 800 μl of PBS buffer and 100 μl of 100 mM SPDP solution was added. The mixture was incubated on a rotator in a cold room (approximately 16 to 20 hours).

[0152] Nanoparticles were purified using a disposable Sephadex PD-10 column using PBS buffer as the eluent. 1000 μl of the eluent was collected. 450 μl of the purified SPDP-functionalized nanoparticles (~1000 μL from the PD-10 column) were mixed with 50 μl of 3% TCEP, and the mixture was allowed to stand at room temperature for 20 minutes. TCEP reduces SPDP to release pyridine-2-thione, which can be detected by absorption spectroscopy. Disulfide reducing agents including DTT (dithiothreitol) or TCEP residues, or other contaminants, were avoided in the mixture to maintain the activity of SPDP on the nanoparticles.

[0153] The reaction mixture was transferred to an Amicon filter unit (0.5 mL, MWCO 100 kDa) and centrifuged in a microcentrifuge at ~10,000 x g (RCF) for 10 minutes. The eluate containing P2T was recovered and used for amine quantification by UV-vis spectroscopy. The nanoparticle agglomerates retained on the filter unit were discarded. The amount of iron in the purified SPDP-functionalized nanoparticle solution was determined using the iron analysis described below, using 8 standard iron solutions and 4 samples.

[0154] Briefly, 10 μL of iron standards and nanoparticle solutions were added to 980 μL of 6N HCl. 10 μL of hydrogen peroxide (H2O2, 30% in H2O) was added to each mixture. A blank sample was prepared by adding 10 μL of distilled water to 980 μL of 6N HCl and 10 μL of H2O2 instead of the iron standards. The iron oxide cores were digested during this process. The optical density (OD) at 410 nm was measured by UV-vis spectroscopy. A calibration curve was obtained using the standards. The concentration of iron content in the nanoparticle solution was determined using the obtained calibration curve.

[0155] The nanoparticle concentration was determined after measuring the iron concentration in the nanoparticle suspension by assuming that each nanoparticle had an average of 2064 iron atoms per nanoparticle. Typically, the concentration was determined to be about 12 mg / mL, which corresponds to a 100 μM nanoparticle solution.

[0156] An unexpected and surprising result was found: by varying the amount of FeCl3 and FeCl2 used in the reaction, the number of amine groups per nanoparticle could be adjusted. Condition 1, which includes both FeCl3 and FeCl2, produces about 60-90 amine groups per nanoparticle. Condition 2 results in the introduction of about 246-500 amine groups per nanoparticle, which is a very high number. An example of a UV-Vis spectrum showing the absorbance of P2T at 410 nm is shown in Figure 6 and 7 middle.

[0157] Amine Quantification

[0158] In an Eppendorf tube, 100 μl of MN was mixed with 100 μl PBS and allowed to reach 4°C. A 20 mM solution of SPDP in DMSO was prepared (1 mg in 100 μl). The cold nanoparticle solution was added dropwise to the SPDP solution (the reaction was exothermic). The solution was incubated for 30 minutes at room temperature (RT). The solution was then purified by a PD-10 column and balanced with PBS by gravity. About 2 mL was collected. Two 350 μl aliquots ("sample" and "control") were placed in two Amicon filters (microcons). 30 μl TCEP (35 mM) was added to the sample and the sample was left alone for 10 minutes. The sample and control were centrifuged at 6000 RPM for 20 minutes at RT. 30 μl TCEP (35 mM) was added to the control eluate. The sample and control were diluted in PBS at a ratio of 1:4.86. The optical density (OD) of the sample and control was read at 343 nm. The number of amine groups is calculated using the formula shown below. In the cuvette, the sample is diluted 20*1.0857*4.86) = 105.53 times. The concentration of iron in the cuvette = the concentration of the iron stock solution / 105.53. [Crystals] in the cuvette = [Fe] in the cuvette / 0.116 (constant) = [Crystals] in μM. [Pyridine-2-thione] in the cuvette = δOD / 0.0081 (extinction coefficient) = [Pyridine-2-thione] in μM NH2 / xtal = [xtals] in the cuvette / [Pyridine-2-thione] in the cuvette.

[0159] Example 5 - Conjugation of oligonucleotides to MN

[0160] As described herein, MNs are functionalized with thiolated oligonucleotides. A stock nanoparticle solution is prepared by mixing 10 mg of Fe (equivalent to approximately 1 mL) in PBS buffer (pH 7.4). Subsequently, the nanoparticles are conjugated to SPDP to provide thiol-reactive ends for the nanoparticles for further conjugation steps. As described above, the SPDP bottle is taken out of the refrigerator and equilibrated to room temperature (approximately 30 minutes) before the bottle is opened to avoid moisture accumulation in the bottle. 10 mg of SPDP is dissolved in 500 μl of anhydrous DMSO, transferred to a cold 13 mL Falcon tube and used immediately. The nanoparticle solution is slowly titrated into the SPDP solution by vortexing and pipetting. Since the SPDP solution hydrolyzes rapidly, a fresh SPDP solution must be prepared each time.

[0161] After incubation overnight in the dark, the nanoparticles were purified using a disposable PD-10 column against PBS buffer (pH 7.4) to remove free, unreacted SPDP molecules. The last portion of the nanoparticle band in the column was discarded to completely separate the free SPDP from the nanoparticles. The concentration of the final nanoparticle solution was calculated using iron analysis. The nanoparticles with thiol-reactive ends were then conjugated to thiol-modified oligonucleotides. The thiol-modified oligonucleotides were dissolved in nuclease-free water to a final concentration of 1 mM. The oligonucleotides were then treated with 3% tris (2-carboxyethyl) phosphine (TCEP) to activate the thiol groups by cleaving the protective disulfide bonds in the oligonucleotide constructs. 3% TCEP was freshly prepared before each use. 100 μl of TCEP solution was added to 1000 μl of oligonucleotide stock solution (1 mM) and incubated for 10 minutes. The oligonucleotides were then purified using ammonium acetate / ethanol precipitation.

[0162] In brief, 500 μl of 9.5M ammonium acetate was added to the oligonucleotide mixture. Afterwards, 2300 μl of cold ethanol (200proof, molecular biology grade) was added to the mixture. White turbid oligonucleotide precipitation was observed in the tube. The solution was then left to stand for 1 hour at -80 ° C. Afterwards, the oligonucleotide mixture was centrifuged at 20,000 × g (RCF) for 15 minutes at 4 ° C. After the centrifugation, a white oligonucleotide mass was formed at the bottom of the tube. The supernatant was discarded, and the mass was washed several times with 100% ethanol and 70% ethanol in water. Then, the mass was dried by a high-speed vacuum concentrator and resuspended in nuclease-free water to a final concentration of 1 mM. Nanoparticles were mixed with activated oligonucleotides in a molar ratio of 1 to 13 (up to 1: 40) on a rotator in a cold room for at least one day. The nanoparticle solution was filtered with a 0.22 μm syringe filter to remove any large contaminants. For in vitro or in vivo studies, 100 μl of nanoparticles were purified using G-50 Sephadex disposable quick spin columns in PBS (pH 7.4).

[0163] Iron analysis, dynamic light scattering, and gel electrophoresis were used to characterize the concentration, size, and oligonucleotide loading of the resulting therapeutic iron oxide nanoprobes. For in vivo studies using small animals, the nanoparticles were concentrated using a 0.5 mL amicon filter unit (MWCO 100 kDa, Amicon Ultra-0.5 mL centrifugal filter) while centrifuging as needed. An example of gel electrophoresis for analyzing oligonucleotide loading is shown in Figure 8 By varying the oligonucleotide to amine / nanoparticle ratio, the oligonucleotide / nanoparticle value can be incrementally increased and fine-tuned.

[0164] Analysis of oligonucleotide loading in polyacrylamide gels

[0165] An appropriate amount (e.g., 10 μl) of TCEP-digested MN is added to an Eppendorf tube. Free oligonucleotides are used as controls to locate bands in the gel and quantify. 2 μl of nucleic acid loading buffer (5×) is added and mixed. Each sample is heated at 70°C for 3 minutes. Each sample is cooled to room temperature and centrifuged quickly. All liquids are carefully loaded on 15% TBE-urea (polyacrylamide) gel or 4%-20% PAGE. The gel is run at 130 volts for about 30-40 minutes using 1×TBE buffer. Carefully remove the gel from the plastic box. The gel is stained for 20 minutes with ethidium bromide (1 μg / mL; 5 μl of stock solution is added to 50 mL of water). The ethidium bromide solution is poured out and saved for proper processing afterwards, and the gel is washed twice with water for about 5 minutes each time. Then, the gel is visualized under UV light.

[0166] Example 6 - Synthesis of magnetic nanoparticles (MN) with controllable magnetic properties

[0167] The synthesis of magnetic nanoparticles (MN) was performed using an exemplary apparatus comprising a glass plate, ice, comprising a round bottom flask. The round bottom flask contained the reaction components described further below. The round bottom flask was placed on a hot plate / stir plate.

[0168] The formulation of MN includes dextran (9 g / 30 mL DI water), 0.54 g ferric chloride, 0.24 g ferrous chloride, and 1 mL NH4OH (28%). This formulation produces the smallest nonlinear index in terms of magnetic properties.

[0169] First, 9 grams of dextran T10 was dissolved in deionized water (DI water) to reach 30 mL (30% w / v) in a conical tube. Dextran T10 (technical quality) is a high purity dextran fraction with an average molecular weight of 10 kDa. When the solution forms a precipitate at room temperature within three days, a fresh dextran solution was prepared.

[0170] Then, the dextran is dissolved in deionized (DI) water on a rotator at room temperature for 1 hour. The resulting solution is colorless, but it may appear slightly turbid with bubbles. Moderate heat may be applied to completely dissolve the dextran. An example of an apparatus for dextran dissolution is shown in Figure 1 .

[0171] The dextran solution was filtered into a 250 mL round bottom flask containing a magnetic stir bar using a 0.2 micron (μm) / 0.45 μm filter. Any remaining dextran in the tube can be rinsed with distilled water as needed. The dissolved solution in the two-necked round bottom flask (RBF) was cooled in an ice bath for 30 minutes with gentle magnetic stirring and nitrogen (or argon) bubbling (not air purging) to remove dissolved oxygen.

[0172] Then, prepare a ferric chloride stock solution. The amount of ferric chloride and ferrous chloride used for "Condition 1" is 0.54g of ferric chloride hexahydrate (FeCl3·6H2O) and 0.2g of ferrous chloride tetrahydrate (FeCl2·4H2O), and the amount of ferric chloride and ferrous chloride used for "Condition 2" is 0.54g of ferric chloride hexahydrate (FeCl3·6H2O) and 0.4g of ferrous chloride tetrahydrate (FeCl2·4H2O). The salts are dissolved in about 5mL of DI water as shown in Table 2. The stock solution is brown, filtered using a 0.22μM filter unit, and stored in a cool, dark place. The amount of iron is calculated by subtracting the other elements in the iron salt composition. The ferrous chloride tetrahydrate bottle is stored in a desiccator to minimize oxidation by air. The powdered ferrous chloride should be green, and the formation of brown crystals in the bottle is an indication of iron oxidation (ie, conversion from Fe(II) to Fe(III)), which should be avoided in order to obtain high quality superparamagnetic nanoparticles.

[0173] Then, a ferrous chloride solution (FeCl2 4H2O) was prepared. 0.2 g of ferrous chloride (condition 1) was freshly weighed and dissolved in 1 mL of DI water in an Eppendorf tube to produce a pearlescent blue-green solution. 0.4 gr of ferrous chloride was used for the recipe of condition 2. To dissolve the ferrous chloride, DI water was purged with nitrogen for 10 minutes (min) to remove oxygen dissolved in the water that can produce non-magnetic oxidized iron (rust). No filtration was required after dissolution, but the dissolution step was performed for 15 minutes (for 0.4 g of ferrous chloride - i.e. condition 1) to ensure complete dissolution. The amount of iron was calculated by ignoring other elements in the iron salt composition.

[0174] 0.545 g of ferric chloride (condition 1 and condition 2) in 1 mL of ferric chloride stock solution was added to the cold dextran solution. 1 mL of ferrous chloride solution (0.2 g FeCl2 (condition 1) or (0.4 g FeCl2 (condition 2)) was added to the flask as shown in Table 2. The mixture was stirred for 1 hour in the flask under continuous nitrogen (or argon) bubbling. All necks of the Rbf were tightly capped with rubber stoppers to prevent oxidation by minimizing air contact, but one neck had a gas outlet with a needle (18G) at the top of the rubber stopper.

[0175] Table 2 - Formulation of magnetic nanoparticles (MN) with controllable magnetic properties

[0176] Condition 1 Condition 2 <![CDATA[FeCl3·6H2O (Iron(III) chloride hexahydrate)]]> 0.54g 0.54g <![CDATA[(FeCl2·4H2O) (Iron(II) chloride tetrahydrate)]]> 0.2g 0.4g Total iron salts added 0.74g 0.94g Total Iron (Fe) Added 168mg 224mg

[0177] Then, stop purging with inactive gas. Connect the cannula to add ammonium hydroxide without air contact. 1mL of concentrated cold (~4°C) ammonium hydroxide (NH4OH, 28%) is quickly added to the reaction mixture in an ice bath. In this step, the stirring speed is set to maximum to overcome the change in viscosity. If the ammonium hydroxide is added slowly, the viscosity increases, thereby interfering with the uniform mixing of the ammonium hydroxide in the ferric / ferrous mixture, producing large particles. Make sure not to add additional ammonium hydroxide or less than 1mL of ammonium hydroxide.

[0178] Table 3

[0179]

[0180] Continue to stir vigorously for 15 minutes in an ice bath. Keep the ice bath below the reaction mixture, and keep stirring during the whole process. After 15 minutes, one neck is connected to a water-cooled condenser, and the other neck is connected to an inactive gas to purge (not in the reaction mixture) under high heat. Be careful not to cause boiling at high temperatures. Reaction Rbf is placed in an oil bath preheated to 90°C. Continue stirring in the oil bath for 60 minutes. The thermometer is kept in the reaction mixture to measure the temperature, and the temperature is maintained at at least about 75°C to 85°C. The heated mixture is no more than 60 minutes. After this step, the airflow is stopped, and the solution is slowly cooled to room temperature. The formation of magnetic nanoparticles coated with dextran is realized at the end of this series of reactions. The volume of the final solution is less than 40mL. Continue stirring for 12 hours at room temperature. The volume is set to 40mL by adding DI water. The solution is transferred to a 50mL conical tube and removed by centrifuging for 1 hour at 14,000RPM. The solution was transferred to an Amicon filter unit (10 mL x 4) and the particles were discarded in a 50 mL conical tube.

[0181] The obtained solution is purified by Amicon tube (50K centrifugal filter unit) to remove unreacted dextran, iron salt and ammonium hydroxide. First, the nanoparticle suspension is concentrated by centrifugation (4,500RPM, 3 hours), which results in a highly concentrated nanoparticle suspension on the filter and a nanoparticle-free eluate below the filter unit. The eluent below the filter is discarded, and the nanoparticle gel-like mass is resuspended in DI water, and the same filter unit is used for centrifugation again. Repeat this step until the eluent shows the pH or neutral pH of DI water. Initially, due to the viscosity of the solution in the mixture, large-sized particles and a large amount of unreacted free dextran, centrifugation takes about 1 hour. However, after the first 3 or 4 centrifugation steps, most of the free dextran is removed, and the resuspension and concentration of nanoparticles are completed in a relatively short centrifugation step (each centrifugation step is about 15 minutes). The washing step is repeated 7 times. The purified solution of the magnetic nanoparticles obtained is resuspended in distilled water. The final volume was adjusted to 21 mL, and the solution was placed in a refrigerator (eg, at about 4° C.) overnight.

[0182] Example 7 - Characterization of magnetic properties of MN

[0183] The samples were analyzed by magnetic particle spectrometry (MPS), and the nonlinear index (NLI) was used as a standard for the magnetic properties of the nanoparticles. Fig. 9 , 11 , 13-14, 16-17, and 19-20 show example MPS analysis data, including the NLI values ​​for each MN sample. The surface modification procedures used for the synthesis and characterization of these MNs were the same as described in the previous examples.

[0184] The magnetic properties are controlled by adjusting the ratio of ferrous chloride to ferric chloride in the reaction mixture. To improve the suspension stability of nanoparticles in aqueous media, the control of magnetic properties is critical. In this system, the surface is designed so that the surface carries a positive charge, which can overcome the magnetic attraction between particles in Brownian motion, which can cause the aggregation / instability of nanoparticles during long-term storage. The degree of amination of each particle is greater than 64, which ensures the suspension stability in aqueous media.

[0185] In terms of magnetism, the nonlinear index (NLI) is a well-characterized property of magnetic particles used to quantify the responsiveness to an external magnetic field. When the particles have stronger magnetism (magnetic permeability) in the absence of an external magnetic field relative to the properties with a given magnetic field applied, the NLI becomes smaller and the relationship shows a nonlinear dependence on the external magnetic field, and is therefore more suitable for imaging and therapeutic techniques that rely on said nonlinearity, an example of which is magnetic particle imaging (MPI).

[0186] Example 8 - Synthesis of MN at different scales

[0187] The synthesis of magnetic nanoparticles (MN) was performed using an exemplary apparatus comprising a glass plate, ice, comprising a round bottom flask. The round bottom flask contained the reaction components described further below. The round bottom flask was placed on a hot plate / stir plate.

[0188] The formulation of MN includes dextran (18 g / 60 mL DI water), 0.54 g ferric chloride, 0.2 g ferrous chloride, and 1 mL NH4OH (28%). This formulation produces the smallest nonlinear index in terms of magnetic properties.

[0189] First, 18 grams of dextran T10 was dissolved in deionized water (DI water) to reach 60 mL (30% w / v) in a conical tube. Dextran T10 (technical quality) is a high purity dextran fraction with an average molecular weight of 10 kDa. When the solution forms a precipitate at room temperature within three days, a fresh dextran solution was prepared.

[0190] Then, the dextran is dissolved in deionized (DI) water on a rotator at room temperature for 1 hour. The resulting solution is colorless, but it may appear slightly turbid with bubbles. Moderate heat may be applied to completely dissolve the dextran. An example of an apparatus for dextran dissolution is shown in Figure 1 .

[0191] The dextran solution was filtered into a 250 mL round bottom flask containing a magnetic stir bar using a 0.2 micron (μm) / 0.45 μm filter. Any remaining dextran in the tube may be rinsed with distilled water as needed. The dissolved solution in the two-necked round bottom flask (Rbf) was cooled in an ice bath for 30 minutes with gentle magnetic stirring and nitrogen (or argon) bubbling (not air purging) to remove dissolved oxygen.

[0192] Then, prepare ferric chloride stock solution. The amount of ferric chloride is 0.54g of ferric chloride hexahydrate in 100mL of DI water, as shown in Table 4 below. The stock solution is brown, filtered using a 0.22μM filter unit, and stored in a cold dark place. The amount of iron is calculated by subtracting other elements in the iron salt composition. The ferrous chloride tetrahydrate bottle is stored in a desiccator to minimize oxidation by air. The powdered ferrous chloride should be green, and the formation of brown crystals in the bottle is an indication of iron oxidation (i.e., conversion from Fe(II) to Fe(III)), which should be avoided in order to obtain high-quality superparamagnetic nanoparticles.

[0193] Then, a ferrous chloride solution (FeCl2·4H2O) was prepared. 0.20 gr of ferrous chloride (Condition 1) was freshly weighed and dissolved in 1 mL of DI water in an Eppendorf tube, producing a pearlescent blue-green solution. 0.4 gr of ferrous chloride was used for the recipe of Condition 2. To dissolve the ferrous chloride, the DI water was purged with nitrogen for 10 minutes (min) to remove dissolved oxygen in the water. No filtration was required after dissolution, but the dissolution step was performed for 10 minutes (for 0.4 g of ferrous chloride - i.e. Condition 1) to ensure complete dissolution was achieved.

[0194] Ferric chloride stock solution was added to the cold dextran solution. 1 mL of ferrous chloride solution 1 equivalent 0.2 g FeCl2 was added to the flask as shown in Table 4. The mixture was stirred in the flask for 1 hour under continuous nitrogen (or argon) bubbling. All the necks of the Rbf were tightly capped with rubber stoppers to prevent oxidation by minimizing air contact, but one neck had a gas outlet with a needle (18G) at the top of the rubber stopper.

[0195] Table 4 - Formulation of magnetic nanoparticles (MN) used for amplification

[0196]

[0197] Then, stop purging with inert gas. Connect a cannula to add ammonium hydroxide without air contact. 1 mL of concentrated cold (~4°C) ammonium hydroxide (NH4OH, 28%) is quickly added to the reaction mixture in an ice bath. In this step, the stirring speed is set to maximum to overcome the change in viscosity. The reaction mixture initially becomes very viscous and turns a military green color. The viscosity is lost after the ammonium hydroxide titration is completed. If the ammonium hydroxide is added slowly, the viscosity increases, thereby interfering with the uniform mixing of the ammonium hydroxide in the ferric / ferrous mixture and producing large particles. Make sure not to add additional ammonium hydroxide or less than 1 mL of ammonium hydroxide.

[0198] Continue to stir vigorously for 15 minutes in an ice bath. Keep in the ice bath below the reaction mixture, and keep stirring during the whole process. After 15 minutes, one neck is connected to a water-cooled condenser, and the other neck is connected to an inactive gas to purge (not in the reaction mixture) under high heat. Be careful not to cause boiling at high temperatures. Reaction Rbf is placed in an oil bath preheated to 60°C. Continue stirring in the oil bath for 90 minutes. The thermometer is kept in the reaction mixture to measure the temperature, and the temperature is maintained at at least about 75°C to 85°C. The heated mixture is no more than 60 minutes. After this step, the airflow is stopped, and the solution is slowly cooled to room temperature. The formation of magnetic nanoparticles coated with dextran is realized at the end of this series of reactions. The volume of the final solution is about 40mL. Stirring is continued for 12 hours at room temperature. The volume is set to 40mL by adding DI water. The solution is transferred to a 50mL conical tube and removed by centrifuging for 1 hour at 14,000RPM. The solution was transferred to an Amicon filter unit (10 mL x 4) and the pellet was discarded in a 50 mL conical tube.

[0199] The obtained solution is purified by Amicon tube (50K centrifugal filter unit) to remove unreacted dextran, iron salt and ammonium hydroxide. First, the nanoparticle suspension is concentrated by centrifugation (4,500RPM, 3 hours), which results in a highly concentrated nanoparticle suspension on the filter and a nanoparticle-free eluate below the filter unit. The eluent below the filter is discarded, and the nanoparticle agglomerate is resuspended in DI water, and the same filter unit is used for centrifugation again. Repeat this step until the eluent shows the pH or neutral pH of DI water. Initially, due to the viscosity of the solution in the mixture, large-sized particles and a large amount of unreacted free dextran, centrifugation takes about 3 hours. However, after the first 3 or 4 centrifugation steps, most of the free dextran is removed, and the resuspension and concentration of nanoparticles are completed in a relatively short centrifugation step (each centrifugation step is about 15 minutes). The washing step is repeated 7 times. The purified solution of the magnetic nanoparticles obtained is resuspended in distilled water. The final volume was adjusted to 21 mL, and the solution was placed in a refrigerator (eg, at about 4° C.) overnight. The sample was analyzed by magnetic particle spectrometer (MPS), and the nonlinear index (NLI) was calculated. The NLI value was used as a standard for the magnetic properties of the nanoparticles.

[0200] In terms of total iron concentration, this amplification study showed an 18-fold amplification greater than the study described in Examples 1-6. The main obstacle overcome was the high viscosity in the iron oxide crystal formation step, the ammonium hydroxide addition step. The use of a mechanical stirrer solves the problem of uniform mixing in the above steps, and the addition of ammonium hydroxide is performed in the shortest possible time by pouring a predetermined volume, and no titration is performed. The volume of ammonium hydroxide is proportional to the amount of total iron compounds, as shown in Table 4. The increase in the total iron concentration of the dextran solution reduces the viscosity in the crystal formation step. These results indicate the mass production of magnetic nanoparticles with excellent nonlinear index under harsh conditions of a total iron concentration of 18 equivalents in 60 mL of dextran solution.

[0201] Other Implementations

[0202] It should be understood that although the invention has been described in conjunction with the detailed description of the invention, the foregoing description is intended to illustrate and not limit the scope of the invention, which is defined by the scope of the appended claims. Other aspects, advantages, and modifications are within the scope of the appended claims.

Claims

1. A nanoparticle composition comprising: Magnetic nanoparticles, the magnetic nanoparticles comprising: Ferric chloride; and with one or more amine-functionalized dextran coatings, wherein the nanoparticle composition does not comprise ferrous chloride, wherein the number of the one or more amine groups ranges from 246 to 500, wherein the dextran is cross-linked with epichlorohydrin, and The nanoparticle composition has tunable amine surface functionalization such that the number of one or more amine groups of the magnetic nanoparticles can be adjusted based on the concentration of ferric chloride.

2. The nanoparticle composition of claim 1, wherein the nanoparticle composition comprises 50 wt% to 100 wt% ferric chloride.

3. The nanoparticle composition of claim 2, wherein the nanoparticle composition comprises 1.2 g of ferric chloride.

4. A nanoparticle composition comprising: Magnetic nanoparticles, the magnetic nanoparticles comprising: Ferric chloride, ferrous chloride, or a combination thereof; and Dextran coating, The nonlinear index of the magnetic nanoparticles ranges from 6 to 40, The diameter of the magnetic nanoparticles is between 40 nm and 200 nm. wherein the dextran is cross-linked with epichlorohydrin, and The nanoparticle composition has tunable amine surface functionalization such that the number of one or more amine groups of the magnetic nanoparticles can be adjusted based on the concentration of one or both of ferric chloride and ferrous chloride.

5. The nanoparticle composition of claim 4, wherein the nanoparticle composition comprises 50 wt% to 80 wt% ferric chloride and 50 wt% to 20 wt% ferrous chloride.

6. The nanoparticle composition of claim 5, wherein the nanoparticle composition comprises 0.54 g of ferric chloride and 0.2 g of ferrous chloride.

7. The nanoparticle composition of claim 6, wherein the nonlinear index of the magnetic nanoparticles ranges from 8 to 14.

8. The nanoparticle composition of claim 4, wherein the nanoparticle composition comprises 0 wt% to 50 wt% ferric chloride and 100 wt% to 50 wt% ferrous chloride, or 80 wt% to 100 wt% ferric chloride and 0 wt% to 20 wt% ferrous chloride.

9. The nanoparticle composition of claim 8, wherein the nanoparticle composition comprises 0.54 g of ferric chloride and 0.4 g of ferrous chloride.

10. The nanoparticle composition according to any one of claims 1 or 4, wherein the magnetic nanoparticles have an iron oxide core with a diameter of 3 nm to 50 nm, and the hydrodynamic diameter of the magnetic nanoparticles is 7 nm to 200 nm.

11. The nanoparticle composition of any one of claims 1 or 4, wherein the polydispersity of the magnetic nanoparticles is 0.1 to 0.

25.

12. The nanoparticle composition of any one of claims 1 or 4, wherein the dextran coating comprises dextran having a molecular weight ranging from 1 kDa to 15 kDa.

13. The nanoparticle composition of any one of claims 1 or 4, wherein the dextran coating comprises dextran having a molecular weight of 10 kDa.

14. The nanoparticle composition of any one of claims 1 or 4, further comprising a drug payload attached to the surface of the dextran coating.

15. The nanoparticle composition of claim 14, wherein the drug payload is an oligonucleotide conjugated to one or more amine groups.

16. The nanoparticle composition of claim 14, wherein the drug payload is a drug, an antibody, a growth factor, a nucleic acid, a nucleic acid derivative, a nucleic acid fragment, a protein, a protein derivative, a protein fragment, a sugar, a polysaccharide fragment, a sugar derivative, a glycoside, a glycoside fragment, a glycoside derivative, an imaging contrast agent, or any combination thereof.

17. A pharmaceutical composition comprising the nanoparticle composition according to any one of claims 1 to 16 and at least one pharmaceutically acceptable carrier or diluent.

18. Use of the nanoparticle composition according to any one of claims 1 to 16 in the preparation of a medicament for use in a method of imaging a tissue target site in a subject in need thereof, the method comprising: administering a therapeutically effective amount of the nanoparticle composition of any one of claims 1-16 to at least the tissue target site at a portion of the subject's body, body part, tissue, cell, or body fluid; applying energy to the magnetic nanoparticle composition and the tissue target site; detecting signals from the nanoparticle composition and the tissue target site; and An image of the tissue target site is obtained based on the detected signals.

19. The use of claim 18, wherein the imaging is magnetic resonance imaging, magnetic particle imaging, or a combination thereof, and the energy is a magnetic field.

20. The use according to claim 18, wherein the disease is cancer and the tissue target site is a tumor.

21. The use of claim 18, wherein the nanoparticle composition accumulates at a target site in the subject.

22. The composition of any one of claims 1 or 4 for use in a method of imaging a disease in a subject in need thereof.

23. A method for preparing a nanoparticle composition according to any one of claims 1 to 3, the method comprising: Dissolve dextran in water; cross-linking the dextran with epichlorohydrin; Prepare ferric chloride solution; preparing a mixture by adding the ferric chloride solution to the dextran; adding a base to the mixture while stirring and placing the mixture in an ice bath; and subjecting the mixture to a temperature of 75°C to 90°C, wherein the step of adding a base prevents the formation of iron oxide crystals, iron oxide hydrates, or a combination thereof, and The mixture comprises 50 wt % to 100 wt % of ferric chloride.

24. A method for preparing a nanoparticle composition according to any one of claims 4 to 16, the method comprising: Dissolve dextran in water; cross-linking the dextran with epichlorohydrin; preparing a ferrous chloride solution, a ferric chloride solution, or a combination thereof; preparing a mixture by adding the ferrous chloride solution, the ferric chloride solution, or a combination thereof to the dextran; adding a base to the mixture while stirring and subjecting the mixture to an ice bath; and subjecting the mixture to a temperature of 75°C to 90°C, wherein the step of adding a base prevents the formation of iron oxide crystals, iron oxide hydrates, or a combination thereof, and The mixture comprises 50 to 80 wt % of ferric chloride and 50 to 20 wt % of ferrous chloride.

Citation Information

Patent Citations

  • Amine Terminated Dextran-Coated Iron Particles and Their Functionalization

    US62943927P0

  • Preparation Method and Application of miRNA-21 Electrochemiluminescence Immunosensor Based on Multifunctionalized Molybdenum Disulfide

    CN106568936B

  • Method for dissociating iron coordination polymer nanoparticles and application thereof

    CN107670036A